Reinforcing films, optical and electronic components

JP7645057B2Active Publication Date: 2025-03-13NITTO DENKO CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020134187
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-06
Publication Date
2025-03-13
Estimated Expiration
2040-08-06

AI Technical Summary

Benefits of technology

【0017】 いくつかの好ましい態様では、前記粘着剤層は触媒を含む。また、前記粘着剤層に含まれる前記触媒と水酸基とのモル比([触媒]/[OH])は1.0×10-6~5.0×10-2である。粘着剤層中の水酸基量に対して所定量以上の触媒を含ませることにより、粘着剤層からの気泡発生が抑制され、平滑な粘着面が得られやすい。また、触媒の使用量を、粘着剤層中の水酸基量に対して所定量以下とすることにより、好適な粘着力上昇を実現しやすい。前記触媒は鉄系触媒であることがより好ましく、前記粘着剤層に含まれる前記触媒と水酸基とのモル比([触媒]/[OH])は1.0×10-4~1.0×10-3であることがさらに好ましい。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645057000004
    Figure 0007645057000004
  • Figure 0007645057000005
    Figure 0007645057000005
  • Figure 0007645057000006
    Figure 0007645057000006
Patent Text Reader

Abstract

To provide a reinforcing film that shows light peelability at first after stuck to an adherend and allows, thereafter, the adhesion to be increased greatly, and has flex recoverability and flex holding power.SOLUTION: A reinforcing film 100 has an adhesive layer 21 having: a polymer (B) that includes a monomer unit having a polyorganosiloxane skeleton and a (meth)acrylic monomer unit ; and a polymer (A), the adhesive layer 21 having a surface elastic modulus of 1-20 kPa at 23°C. The adhesive layer 21 has a bulk elastic modulus G' of 10-200 kPa at 23°C and a bulk elastic modulus G' of 5-100 kPa at 80°C, and has a tanδ of 0.10-0.60 at 80°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a reinforcing film, and an optical member and an electronic member to which the reinforcing film is attached. [Background technology]

[0002] Adhesives in the form of adhesive sheets are widely used in various applications in portable electronic devices such as mobile phones, smartphones, and tablet computers, as well as other electronic devices, for the purpose of bonding adherends together or fixing articles to adherends. For example, adhesive sheets are used as reinforcing materials (reinforcing films) that impart rigidity and impact resistance to optical components and electronic components that constitute the above-mentioned devices. Patent Documents 1 and 2 are cited as documents disclosing this type of prior art.

[0003] Moreover, in recent years, portable electronic devices that can be bent or rolled have been attracting attention, and the development of adhesive sheets that can be used for fixing flexible devices (typically image display devices such as organic electroluminescence (EL) and liquid crystal display devices) built into such electronic devices is progressing (Patent Documents 3 to 6).

[0004] Meanwhile, looking at the performance of the adhesive, recently, an adhesive sheet has been proposed that exhibits low adhesive strength when first applied to an adherend, and then can increase its adhesive strength significantly (Patent Document 7). An adhesive sheet with such properties exhibits reworkability (reworkability) that is useful for preventing a decrease in yield due to incorrect or failed application of the adhesive sheet before the increase in adhesive strength, and can exhibit strong adhesiveness that is suitable for the original intended use of the adhesive sheet after the increase in adhesive strength. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6366199 [Patent Document 2] Patent No. 6366200 [Patent Document 3] Patent No. 6376271 [Patent Document 4] JP 2016-108555 A [Patent Document 5] JP 2017-095657 A [Patent Document 6] JP 2017-095659 A [Patent Document 7] Patent No. 6373458 Summary of the Invention [Problem to be solved by the invention]

[0006] The reinforcing film may also be used in the flexible device. For example, in the manufacture of the flexible device, since the members constituting the device are often thin, it is desirable to apply a pressure-sensitive adhesive sheet as a reinforcing film to reinforce the device, prevent defects caused by deformation of the device, and improve handling. Since the flexible device may be repeatedly folded or bent, the reinforcing film used in the flexible device is required to have a property (bending recovery) that allows the device to recover to a normal shape even when repeatedly bent, and a property (bending retention) that prevents defects such as peeling. A reinforcing film having such bending recovery and bending retention can be used for various applications including flexible devices, and is therefore useful with few limitations on the range of application.

[0007] For example, as proposed in Patent Document 7, an adhesive that shows low adhesion at the beginning of application and then increases significantly in adhesion is also desirable to have flex recovery and flex retention when used as a reinforcing film. One method for improving flex retention is, for example, appropriately setting the storage modulus of the adhesive. However, in an adhesive designed to increase in adhesion as described above, if the storage modulus is changed, both the initial low adhesion and the adhesion after increase are affected. Also, when considering flex recovery in addition to flex retention, it is not easy to satisfy all of these characteristics. It would be practically useful to improve flex recovery and flex retention for an adhesive that shows low adhesion at the beginning of application and then increases significantly in adhesion.

[0008] The present invention has been made in view of the above circumstances, and aims to provide a reinforcing film that exhibits easy peelability in the early stages after being attached to an adherend, and that is capable of significantly increasing its adhesive strength thereafter, and that has flex recovery and flex retention. Another aim of the present invention is to provide an optical member and an electronic member to which the reinforcing film is attached. [Means for solving the problem]

[0009] According to the present specification, there is provided a reinforcing film including a pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer includes a polymer (A) and a polymer (B). The polymer (B) includes a monomer unit having a polyorganosiloxane skeleton and a (meth)acrylic monomer unit. The pressure-sensitive adhesive layer has a surface elastic modulus of 1 to 20 kPa at 23°C.

[0010] According to the above configuration, the adhesive layer contains the polymer (A) and the polymer (B) containing a monomer unit having a polyorganosiloxane skeleton, so that it shows light peelability in the initial stage of being attached to the adherend, and thereafter, it is possible to greatly increase the adhesive strength. In addition, the reinforcing film has flex recovery and flex retention. Specifically, a reinforcing film in which the surface modulus of elasticity at 23°C (23°C surface modulus) of the adhesive layer is 1 kPa or more has good flex recovery while exhibiting the above-mentioned adhesive properties. In addition, since the 23°C surface modulus of elasticity of the adhesive layer is 20 kPa or less, it has good flex retention while exhibiting the above-mentioned adhesive properties, so that even when used in a manner in which it is repeatedly folded, problems such as peeling are unlikely to occur.

[0011] In some preferred embodiments of the technology disclosed herein (including reinforcing films, optical members, and electronic members, the same applies below), the pressure-sensitive adhesive layer has a bulk modulus G′ at 23° C. 23 The bulk modulus G' in this range is 10 to 200 kPa. 23 The adhesive having such a structure tends to have an initial adhesive strength in a suitable range that provides excellent peelability. It also has excellent processability and generally tends to provide both strain relaxation and flex recovery at room temperature.

[0012] In some preferred embodiments, the pressure-sensitive adhesive layer has a bulk modulus G′ at 80° C. 80 The bulk modulus G' in this range is 5 to 100 kPa. 80 Generally, the adhesive having the above structure is likely to achieve both flex recovery and flex retention. For example, even when used under high temperature conditions of about 80°C, the adhesive has an elasticity suitable for flex recovery and an adhesive retention that realizes flex retention.

[0013] In some preferred embodiments, the pressure-sensitive adhesive layer has a tan δ 80 is 0.10 to 0.60. 80 (Loss modulus at 80℃ G″ 80 / Storage modulus G' at 80℃ 80) is 0.10 or more, the adhesive is likely to exhibit an adhesive strength suitable for bending and holding. 80 By making the ratio of the bending moment to the bending moment of the adhesive being 0.60 or less, the adhesive is prevented from undergoing plastic deformation, and good bending recovery is easily obtained. In addition, even when the reinforcing film is kept in a bent state for a long period of time, the reinforcing film is likely to exhibit a holding force (bending holding force) that does not cause peeling from the adherend.

[0014] The polymer (A) is preferably an acrylic polymer. The adhesive layer containing the polymer (A) which is an acrylic polymer and the polymer (B) containing a monomer unit having a polyorganosiloxane skeleton preferably achieves the effects of the technology disclosed herein.

[0015] In some preferred embodiments, the content of the polymer (B) in the pressure-sensitive adhesive layer is 0.5 to 5 parts by weight relative to 100 parts by weight of the polymer (A). By making the amount of the polymer (B) 0.5 parts by weight or more relative to 100 parts by weight of the polymer (A), it is easy to obtain light peelability at the initial stage of application. By making the amount of the polymer (B) 5 parts by weight or less, it is easy to realize the desired increase in adhesive strength. In addition, by making the amount of the polymer (B) used within the above range, it is easy to realize good bending recovery and bending retention.

[0016] In some preferred embodiments, the molar ratio ([NCO] / [OH]) of the isocyanate group to the hydroxyl group contained in the pressure-sensitive adhesive layer is 0.002 to 0.03. A pressure-sensitive adhesive layer having the molar ratio ([NCO] / [OH]) of 0.002 or more tends to have excellent bending recovery and excellent processability. In addition, by setting the molar ratio ([NCO] / [OH]) to 0.03 or less, a suitable increase in adhesive strength tends to be easily achieved. In the pressure-sensitive adhesive layer, the isocyanate group and the hydroxyl group may be present in a state where at least a part of them are chemically bonded (crosslinked). The pressure-sensitive adhesive layer contains, for example, a crosslinking agent, and in such a configuration, the isocyanate group may be, for example, a part of the crosslinking agent, and the hydroxyl group may be, for example, a part of the polymer (A).

[0017] In some preferred embodiments, the pressure-sensitive adhesive layer contains a catalyst. The molar ratio of the catalyst to hydroxyl groups ([catalyst] / [OH]) contained in the pressure-sensitive adhesive layer is 1.0×10 -6 ~5.0×10 -2 By including a catalyst in a predetermined amount or more relative to the amount of hydroxyl groups in the adhesive layer, the generation of bubbles from the adhesive layer is suppressed, and a smooth adhesive surface is easily obtained. In addition, by using a catalyst in an amount equal to or less than a predetermined amount relative to the amount of hydroxyl groups in the adhesive layer, it is easy to achieve a suitable increase in adhesive strength. The catalyst is more preferably an iron-based catalyst, and the molar ratio of the catalyst to hydroxyl groups ([catalyst] / [OH]) contained in the adhesive layer is 1.0×10 -4 ~1.0×10 -3 It is even more preferable that:

[0018] The reinforcing film disclosed herein is suitable as a reinforcing film that imparts rigidity and impact resistance to an optical member such as a polarizing plate, a wavelength plate, etc., during processing or transport of the optical member. Thus, according to the present specification, there is provided an optical member to which any of the reinforcing films disclosed herein is attached.

[0019] The reinforcing film disclosed herein is also suitable as a reinforcing film for electronic components of devices such as portable electronic devices, etc. Thus, according to the present specification, there is provided an electronic component to which any of the reinforcing films disclosed herein is attached. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic configuration of a reinforcing film according to an embodiment. [Diagram 2] FIG. 4 is a cross-sectional view illustrating a schematic configuration of a reinforcing film according to another embodiment. [Diagram 3] FIG. 4 is a cross-sectional view illustrating a schematic configuration of a reinforcing film according to another embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Preferred embodiments of the present invention will be described below. Matters necessary for carrying out the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on carrying out the invention described in this specification and the common general technical knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general technical knowledge in the relevant field. In the following drawings, the same reference numerals may be used to denote components or parts having the same function, and duplicated descriptions may be omitted or simplified. In addition, the embodiments shown in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the size or scale of the product actually provided.

[0022] In addition, in this specification, the term "acrylic polymer" refers to a polymer containing a monomer unit derived from a (meth)acrylic monomer in the polymer structure, and typically refers to a polymer containing a monomer unit derived from a (meth)acrylic monomer at a ratio of more than 50% by weight. In addition, the term "(meth)acrylic monomer" refers to a monomer having at least one (meth)acryloyl group in one molecule. Here, the term "(meth)acryloyl group" refers to an acryloyl group and a methacryloyl group in a comprehensive sense. Therefore, the concept of the (meth)acrylic monomer here can include both a monomer having an acryloyl group (acrylic monomer) and a monomer having a methacryloyl group (methacrylic monomer). Similarly, in this specification, "(meth)acrylic acid" refers to acrylic acid and methacrylic acid, and "(meth)acrylate" refers to acrylate and methacrylate in a comprehensive sense.

[0023] <Structural example of reinforcing film> The reinforcing film disclosed herein has the form of an adhesive sheet having an adhesive surface formed by an adhesive. The adhesive sheet used as the reinforcing film is configured to include an adhesive layer. The reinforcing film disclosed herein may be in the form of an adhesive sheet with a substrate in which the adhesive layer is laminated on one or both sides of a supporting substrate, or may be in the form of a substrate-less adhesive sheet that does not have a supporting substrate. Hereinafter, the supporting substrate may be simply referred to as a "substrate". In this specification, the term "reinforcing film" refers to an adhesive sheet (reinforcing adhesive film) used to reinforce an adherend as described below. The reinforcing film is not limited to the form of an adhesive sheet with a substrate, for example, since it can be reinforced by attaching a support material or the like to one adhesive surface of the reinforcing film and then attaching the other adhesive surface to the adherend to be reinforced. In this respect, it is understood as a broader concept than the "reinforcing film" described below, which has the form of an adhesive sheet with a substrate.

[0024] The structure of a reinforcing film according to one embodiment is shown in FIG. 1. The reinforcing film 1 is configured as a substrate-attached single-sided adhesive sheet including a sheet-like supporting substrate 10 having a first surface 10A and a second surface 10B, and an adhesive layer 21 provided on the first surface 10A side. The adhesive layer 21 is fixed to the first surface 10A side of the supporting substrate 10. The reinforcing film 1 is used by attaching the adhesive layer 21 to an adherend. The reinforcing film 1 before use (i.e., before being attached to an adherend) can be a component of a release-liner-attached reinforcing film 100 in a form in which the surface (adhesive surface) 21A of the adhesive layer 21 is in contact with a release liner 31, at least the side facing the adhesive layer 21 being a release surface (release surface), as shown in FIG. As the release liner 31, for example, one configured to be a release surface by providing a release layer made of a release treatment agent on one side of a sheet-like substrate (liner substrate) can be preferably used. Alternatively, the release liner 31 may be omitted, a supporting substrate 10 having a release surface at its second surface 10B is used, and the reinforcing film 1 may be rolled up so that the adhesive surface 21A is in contact with the second surface 10B of the supporting substrate 10 (roll form). When attaching the reinforcing film 1 to an adherend, the release liner 31 or the second surface 10B of the supporting substrate 10 is peeled off from the adhesive surface 21A, and the exposed adhesive surface 21A is pressure-bonded to the adherend.

[0025] The structure of a reinforcing film according to another embodiment is shown in FIG. 2. The reinforcing film 2 is configured as a substrate-attached double-sided adhesive sheet including a sheet-like supporting substrate 10 having a first surface 10A and a second surface 10B, an adhesive layer 21 provided on the first surface 10A side, and an adhesive layer 22 provided on the second surface 10B side. The adhesive layer (first adhesive layer) 21 is fixed to the first surface 10A of the supporting substrate 10, and the adhesive layer (second adhesive layer) 22 is fixed to the second surface 10B of the supporting substrate 10. The reinforcing film 2 is used by attaching the adhesive layers 21 and 22 to different locations of an adherend. The locations to which the adhesive layers 21 and 22 are attached may be locations of different members, or may be different locations within a single member. As shown in Fig. 2, the reinforcing film 2 before use may be a component of a reinforcing film 200 with a release liner in which the surface (first adhesive surface) 21A of the adhesive layer 21 and the surface (second adhesive surface) 22A of the adhesive layer 22 are in contact with release liners 31, 32, each of which has a release surface facing at least the adhesive layers 21, 22. As the release liners 31, 32, for example, a sheet-like substrate (liner substrate) may be preferably used, in which a release layer made of a release treatment agent is provided on one side of the substrate so that the one side serves as a release surface. Alternatively, the release liner 32 may be omitted, and a release liner 31 having both release surfaces may be used, which is superimposed on the reinforcing film 2 and wound in a spiral shape to form a reinforcing film with a release liner in which the second adhesive surface 22A is in contact with the back surface of the release liner 31 (roll form).

[0026] The structure of a reinforcing film according to yet another embodiment is shown in FIG. 3. The reinforcing film 3 is configured as a substrate-less double-sided adhesive sheet made of an adhesive layer 21. The reinforcing film 3 is used by attaching a first adhesive surface 21A formed by one surface (first surface) of the adhesive layer 21 and a second adhesive surface 21B formed by the other surface (second surface) of the adhesive layer 21 to different positions on an adherend. The reinforcing film 3 before use may be a component of a reinforcing film 300 with a release liner in which the first adhesive surface 21A and the second adhesive surface 21B are in contact with release liners 31 and 32, each of which has a release surface at least on the side facing the adhesive layer 21, as shown in FIG. 3. Alternatively, the release liner 32 may be omitted, and a release liner 31 with both sides being release surfaces may be used, which is superimposed on the reinforcing film 3 and wound in a spiral shape to form a reinforcing film with a release liner in which the second adhesive surface 21B is in contact with the back surface of the release liner 31 (roll form).

[0027] The reinforcing film may be in the form of a roll or a sheet, and may be cut, punched, or otherwise processed into an appropriate shape depending on the application or mode of use. The pressure-sensitive adhesive layer in the technology disclosed herein is typically formed continuously, but is not limited thereto, and may be formed in a regular or random pattern, such as a dotted or striped pattern.

[0028] <Adhesive layer> The reinforcing film disclosed herein includes a pressure-sensitive adhesive layer containing a polymer (A) and a polymer (B). Such a pressure-sensitive adhesive layer may be formed from a pressure-sensitive adhesive composition containing a polymer (A) that is a complete or partial polymer of a monomer raw material A, and a polymer (B). The form of the pressure-sensitive adhesive composition is not particularly limited, and may be in various forms, such as a solvent type, a water-dispersed type, a hot melt type, or an active energy ray curable type (e.g., a photocurable type).

[0029] (Surface elasticity at 23℃) The adhesive layer disclosed herein is characterized in that the surface modulus of elasticity at 23° C. (23° C. surface modulus) of its surface (adhesive surface) is within the range of 1 to 20 kPa. When the 23° C. surface modulus is 1 kPa or more, good flex recovery can be achieved while realizing the adhesive properties based on the inclusion of polymer (A) and polymer (B). Furthermore, when the surface modulus is 20 kPa or less, good flex retention can be achieved while realizing the adhesive properties.

[0030] From the viewpoint of improving flex recovery, the 23°C surface elastic modulus is preferably 2 kPa or more, more preferably 3 kPa or more, and even more preferably 4 kPa or more (e.g., 5 kPa or more), and may be 8 kPa or more, 10 kPa or more, or 12 kPa or more (e.g., 14 kPa or more). The higher the surface elastic modulus, the better the initial easy peelability tends to be. In addition, from the viewpoint of favorably expressing an increase in adhesive strength while achieving both good flex recovery and flex retention, the 23°C surface elastic modulus is suitably 15 kPa or less, preferably 12 kPa or less, more preferably 9 kPa or less, and even more preferably 7 kPa or less (e.g., 6 kPa or less), and may be 4 kPa or less.

[0031] The 23°C surface elastic modulus of the pressure-sensitive adhesive layer can be adjusted by the type and characteristics (molecular weight, glass transition temperature, molecular structure, etc.) of polymer (A), the type (chemical structure, etc.) and characteristics (molecular weight, glass transition temperature, etc.) of polymer (B), the amount used, the type and amount used of crosslinking agent, etc. The 23°C surface elastic modulus of the pressure-sensitive adhesive layer is measured by the method described in the Examples below.

[0032] (23℃ Bulk elastic modulus G′ 23 ) Bulk elastic modulus G' of adhesive layer at 23℃ 23 (23℃ Bulk elastic modulus G′ 23 ) is appropriately set within a range that satisfies the above-mentioned range of the surface elastic modulus at 23°C, and is not limited to a specific range. In some embodiments, the 23°C bulk elastic modulus G' of the pressure-sensitive adhesive layer is 23 It is appropriate that the bulk elastic modulus G' is 10 kPa or more.23 By setting the bulk elastic modulus G' to a predetermined value or more, the adhesive strength at the initial stage of application tends to be in a suitable range that provides excellent light peelability. In addition, the processability is excellent, and generally, the flex recovery property at room temperature tends to be excellent. 23 In some other embodiments, the bulk elastic modulus G' is preferably 15 kPa or more, more preferably 20 kPa or more, even more preferably 25 kPa or more, and particularly preferably 30 kPa or more. 23 may be 50 kPa or more, 80 kPa or more, or 100 kPa or more.

[0033] In some embodiments, the 23° C. bulk modulus G′ of the adhesive layer 23 The bulk elastic modulus G' should be 200 kPa or less. 23 Generally, a pressure-sensitive adhesive having a bulk modulus G' of not more than a certain value tends to have excellent strain relaxation properties at room temperature and is also prone to exhibiting increased adhesive strength. 23 In some preferred embodiments, the bulk elastic modulus G' is preferably 150 kPa or less, more preferably 90 kPa or less. 23 The pressure may be 60 kPa or less, or 40 kPa or less (eg, 35 kPa or less).

[0034] (80℃ Bulk elastic modulus G′ 80 ) Bulk elastic modulus G' of adhesive layer at 80℃ 80 (80℃ Bulk elastic modulus G′ 80 ) is appropriately set within the range satisfying the above-mentioned range of the surface elastic modulus at 23°C, and is not limited to a specific range. In some embodiments, the 80°C bulk elastic modulus G' of the pressure-sensitive adhesive layer is 80 The bulk elastic modulus G' is preferably 5 kPa or more. 80 By setting the bulk elastic modulus G' to a predetermined value or more, the flex recovery is generally improved, and the material can have elasticity suitable for flex recovery even when used under high temperature conditions. 80In some other embodiments, the bulk modulus G′ may be 7 kPa or more, 9 kPa or more, or 10 kPa or more. 80 may be 15 kPa or more, 30 kPa or more, or 50 kPa or more.

[0035] In some embodiments, the 80° C. bulk modulus G′ of the adhesive layer 80 The bulk elastic modulus G' should be 100 kPa or less. 80 By limiting the bulk elastic modulus G' to a predetermined value or less, it is generally easy to obtain good bending retention and to achieve both bending recovery and bending retention. For example, it is possible to obtain a material that has elasticity suitable for bending recovery and adhesive retention that realizes bending retention in various environments including high temperature conditions. 80 In some embodiments, the bulk modulus G' is preferably 90 kPa or less, and more preferably 60 kPa or less. 80 may be 20 kPa or less, 16 kPa or less, or 14 kPa or less (for example, 12 kPa or less).

[0036] (80℃ tanδ 80 ) Tan δ of adhesive layer at 80℃ 80 (80℃ tanδ 80 ) is appropriately set within a range that satisfies the above-mentioned range of the surface elastic modulus at 23°C, and is not limited to a specific range. 80 It is appropriate that tan δ is 0.10 or more. 80 The higher the tan δ, the more likely the adhesive will exhibit adhesive strength suitable for bending and maintaining the bending strength. 80 is preferably 0.20 or more. In some preferred embodiments, the tan δ 80 may be 0.30 or more, 0.40 or more, or 0.45 or more.

[0037] In some embodiments, the 80° C. tan δ of the adhesive layer 80 is preferably 0.60 or less.80 By being 0.60 or less, the plastic deformation of the adhesive is suppressed, and good bending recovery is easily obtained. In addition, even if the reinforcing film is held in a bent state for a long time, it is easy to exhibit a holding force that does not cause peeling from the adherend. Furthermore, the increase in adhesive strength is also likely to be in a suitable range. 80 In some other embodiments, the 80° C. tan δ may be 0.55 or less. 80 may be 0.50 or less, or may be 0.35 or less.

[0038] Bulk elastic modulus G' of adhesive layer at 23℃ 23 , 80℃ Bulk modulus G′ 80 and 80℃ tan δ 80 can be adjusted by the type and characteristics (molecular weight, glass transition temperature, molecular structure, etc.) of polymer (A), the type (chemical structure, etc.) and characteristics (molecular weight, glass transition temperature, etc.) of polymer (B), the amount used, the type and amount used of crosslinking agent, etc. 23 , 80℃ Bulk modulus G′ 80 and 80℃ tan δ 80 is measured by the method described in the Examples below.

[0039] (Polymer (A)) As the polymer (A), one or more of various polymers that exhibit rubber elasticity at room temperature, such as acrylic polymers, rubber polymers, polyester polymers, urethane polymers, polyether polymers, silicone polymers, polyamide polymers, and fluorine polymers, known in the field of pressure-sensitive adhesives, can be used. In the reinforcing film disclosed herein, the polymer (A) is typically the main component of the polymer components contained in the pressure-sensitive adhesive layer, i.e., a component that accounts for more than 50% by weight, and may be a component that accounts for 75% by weight or more of the above polymer components. In some embodiments, the polymer (A) is a component that accounts for more than 50% by weight of the entire pressure-sensitive adhesive layer, and may be a component that accounts for 70% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more (e.g., 97% by weight or more).

[0040] Glass transition temperature T of polymer (A) A is not particularly limited and can be selected to obtain preferred properties in the reinforcing film disclosed herein. In some embodiments, T A A polymer (A) having a temperature of less than 0° C. can be preferably used. Since a pressure-sensitive adhesive containing such a polymer (A) exhibits appropriate fluidity (e.g., mobility of the polymer chain contained in the pressure-sensitive adhesive), it is suitable for realizing a reinforcing film whose adhesive strength increases to a predetermined value or more upon heating. The reinforcing film disclosed herein has a temperature of less than 0° C. A may be preferably carried out using a polymer (A) having a temperature of less than -10°C, less than -20°C, less than -30°C or less than -35°C. A may be less than -40°C or less than -50°C. In some preferred embodiments, T A is -55°C or lower, more preferably -58°C or lower, further preferably -62°C or lower, and may be -65°C or lower (e.g., -66°C or lower). A There is no particular restriction on the lower limit of T. From the viewpoint of material availability and improving the cohesive strength of the adhesive layer, T A Preferably, the polymer (A) has a temperature of -80°C or higher, or -70°C or higher. A may be, for example, -63°C or higher, -55°C or higher, -50°C or higher, or -45°C or higher.

[0041] In this specification, the glass transition temperature (Tg) of polymers including polymer (A) and polymer (B) described later refers to a nominal value described in literature, catalogs, etc., or a Tg calculated by Fox's formula based on the composition of the monomer raw material used in the preparation of the polymer. The Fox formula is a relational expression between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg=Σ(Wi / Tgi) In the above Fox formula, Tg represents the glass transition temperature (unit: K) of the copolymer, Wi represents the weight fraction (copolymerization ratio by weight) of monomer i in the copolymer, and Tgi represents the glass transition temperature (unit: K) of a homopolymer of monomer i. When the target polymer for which Tg is specified is a homopolymer, the Tg of the homopolymer and the Tg of the target polymer are the same.

[0042] The glass transition temperature of the homopolymer used to calculate Tg is a value listed in a publicly known document. Specifically, the values ​​are listed in "Polymer Handbook" (3rd Edition, John Wiley & Sons, Inc., 1989). For monomers for which multiple values ​​are listed in the Polymer Handbook, the highest value is used.

[0043] As the glass transition temperature of a homopolymer of a monomer not described in the Polymer Handbook, a value obtained by the following measurement method is used. Specifically, 100 parts by weight of monomer, 0.2 parts by weight of 2,2'-azobisisobutyronitrile, and 200 parts by weight of ethyl acetate as a polymerization solvent are charged into a reactor equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a reflux condenser tube, and stirred for 1 hour while passing nitrogen gas through it. After removing oxygen from the polymerization system in this way, the temperature is raised to 63°C and the reaction is carried out for 10 hours. Then, the mixture is cooled to room temperature to obtain a homopolymer solution with a solid content concentration of 33% by weight. Then, the homopolymer solution is cast and applied onto a release liner, and dried to prepare a test sample (sheet-shaped homopolymer) with a thickness of about 2 mm. This test sample was punched out into a disk with a diameter of 7.9 mm, sandwiched between parallel plates, and the viscoelasticity was measured in shear mode using a viscoelasticity tester (TA Instruments Japan, model name "ARES") while applying a shear strain of 1 Hz at a temperature range of -70°C to 150°C and a heating rate of 5°C / min. The temperature corresponding to the peak top temperature of tan δ was taken as the Tg of the homopolymer.

[0044] Although not particularly limited, the weight average molecular weight (Mw) of the polymer (A) is usually about 20×10 4 It is appropriate that the Mw of the polymer (A) is 30×10 or more. A PSA exhibiting good cohesiveness is easily obtained by using the polymer (A) having such Mw. From the viewpoint of obtaining higher cohesive strength, in some preferred embodiments, the Mw of the polymer (A) is, for example, 30×10 4 It may be 40×10 or more. 4 More than 50 x 10 is fine. 4 More than 60 x 10 is fine. 4 More than 80 x 10 is fine. 4 The Mw of the polymer (A) is usually about 500×10 4 It is appropriate that the Mw of the polymer (A) is not too high. Since the polymer (A) with such Mw is likely to form an adhesive that exhibits moderate fluidity (mobility of the polymer chain), it is suitable for realizing a reinforcing film that has low initial adhesive strength after application and a large increase in adhesive strength. It is also preferable from the viewpoint of improving compatibility with the polymer (B) that the Mw of the polymer (A) is not too high. In some preferred embodiments, the Mw of the polymer (A) is, for example, 250×10 4 may be less than or equal to 200 x 10 4 Less than 150×10 is also fine. 4 Less than 100 x 10 4 Less than 70×10 is fine. 4 The following is also fine.

[0045] In this specification, the Mw of the polymer (A) and the polymer (B) described later can be determined in terms of polystyrene by gel permeation chromatography (GPC). More specifically, the Mw can be measured according to the method and conditions described in the examples described later.

[0046] As the polymer (A) in the reinforcing film disclosed herein, an acrylic polymer can be preferably used. When an acrylic polymer is used as the polymer (A), good compatibility with the polymer (B) tends to be easily obtained. Good compatibility between the polymer (A) and the polymer (B) is preferable because it can contribute to reducing the initial adhesive strength and improving the adhesive strength after heating through improving the mobility of the polymer (B) in the adhesive layer. In addition, an acrylic polymer, which has a high degree of freedom in molecular design, is suitable as an adhesive material that can improve adhesive properties, bending recovery, and bending retention in a balanced manner.

[0047] The acrylic polymer may be, for example, a polymer containing 50% by weight or more of monomer units derived from (meth)acrylic acid alkyl esters, that is, a polymer in which 50% by weight or more of the total amount of the monomer component (monomer raw material A) for preparing the acrylic polymer is a (meth)acrylic acid alkyl ester. The (meth)acrylic acid alkyl ester may be a monomer unit having 1 to 20 carbon atoms (i.e., C 1-20 Of the monomer raw materials A, (meth)acrylic acid alkyl esters having a linear or branched alkyl group are preferably used. 1-20 The proportion of alkyl ester may be, for example, 50% by weight or more, or 60% by weight or more. In some preferred embodiments, the (meth)acrylic acid C in the monomer raw material A is 1-20 The proportion of alkyl ester is 70% by weight or more, more preferably 80% by weight or more, even more preferably 85% by weight or more, and particularly preferably 90% by weight or more. By using an acrylic polymer with such a monomer composition, it is easy to obtain a pressure-sensitive adhesive that has a good balance between increased adhesive strength, flex recovery, and flex retention. In addition, (meth)acrylic acid C in the monomer raw material A is 1-20 The proportion of alkyl ester may be, for example, 99.9% by weight or less, 98% by weight or less, or 95% by weight or less. 1-20The proportion of alkyl esters may be, for example, 90% by weight or less, 85% by weight or less, or 80% by weight or less.

[0048] (Meth)acrylic acid C 1-20 Non-limiting examples of alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl ... and isopropyl (meth)acrylate. Examples of such acrylates include isooctyl, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate.

[0049] Among these, at least (meth)acrylic acid C 1-18 It is preferable to use an alkyl ester, and at least (meth)acrylic acid C 1-14 It is more preferred to use alkyl esters. In some embodiments, the acrylic polymer is (meth)acrylic acid C 4-12 Alkyl ester (preferably acrylic acid C 4-10 Alkyl esters, such as acrylic acid C 6-10 The acrylic polymer may contain at least one selected from the group consisting of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) as a monomer unit. For example, an acrylic polymer containing one or both of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) is preferred, and an acrylic polymer containing at least 2EHA is particularly preferred.

[0050] In some preferred embodiments, acrylic acid C is included in the monomer raw material A for preparing an acrylic polymer. 6-10 Alkyl ester (preferably acrylic acid C 8-9 The proportion of alkyl ester, typically 2EHA) is 70% by weight or more, more preferably 80% by weight or more, even more preferably 85% by weight or more, and particularly preferably 90% by weight or more. An acrylic polymer having such a monomer composition is particularly suitable for achieving the effects of the technology disclosed herein. In addition, acrylic acid C in the monomer raw material A is 6-10 Alkyl ester (preferably acrylic acid C 8-9 The proportion of the alkyl ester (typically 2EHA) may be, for example, 99.9% by weight or less, and from the viewpoints of initial low adhesion, flex recovery, etc., it may be 98% by weight or less, or 95% by weight or less.

[0051] In some preferred embodiments, the monomer raw material A for preparing an acrylic polymer contains (meth)acrylic acid C 1-3 Alkyl esters (e.g. (meth)acrylic acid C 1 It is preferred that the proportion of alkyl esters, typically methyl methacrylate (MMA), is limited. 1-3 Alkyl esters (e.g. (meth)acrylic acid C 1 (Meth)acrylic acid C (alkyl ester, typically MMA) tends to have a relatively high Tg, and adhesives containing acrylic polymers using the above monomer components tend to have high cohesiveness. 1-3 By limiting the amount of alkyl ester used, the cohesive strength of the adhesive can be appropriately reduced, and an elastic modulus (typically a surface elastic modulus) suitable for achieving both bending retention and increased adhesive strength can be preferably realized. From this viewpoint, (meth)acrylic acid C of the monomer raw material A is preferably used. 1-3 Alkyl esters (e.g. (meth)acrylic acid C 1The proportion of alkyl ester (typically MMA) is suitably 8% by weight or less, preferably 6% by weight or less, more preferably 3% by weight or less, and further preferably 1% by weight or less (for example, 0 to 0.3% by weight).

[0052] The monomer raw material A may contain, as the main component, an alkyl (meth)acrylate ester and, if necessary, another monomer (copolymerizable monomer) that can be copolymerized with the alkyl (meth)acrylate ester. As the copolymerizable monomer, a monomer having a polar group (e.g., a carboxyl group, a hydroxyl group, a nitrogen atom-containing ring, etc.) can be suitably used. The monomer having a polar group can be useful for introducing a crosslinking point into the acrylic polymer or for increasing the cohesive force of the acrylic polymer. The copolymerizable monomer can be used alone or in combination of two or more kinds.

[0053] Non-limiting examples of copolymerizable monomers include the following: Hydroxyl group-containing monomers: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. Monomers having a nitrogen atom-containing ring: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylmorpholine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, N-vinylpyridazine, etc.; For example, monomers having a succinimide skeleton, such as N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, and N-(meth)acryloyl-8-oxyhexamethylene succinimide; Maleimides, such as, for example, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, and the like; and For example, itaconimides such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide. Carboxy group-containing monomers: for example, acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and the like. Acid anhydride group-containing monomers: for example, maleic anhydride, itaconic anhydride. Epoxy group-containing monomers: for example, epoxy group-containing acrylates such as glycidyl (meth)acrylate and 2-ethyl glycidyl ether (meth)acrylate, allyl glycidyl ether, and glycidyl ether (meth)acrylate. Cyano group-containing monomers: for example, acrylonitrile, methacrylonitrile, etc. Isocyanate group-containing monomers: for example, 2-isocyanatoethyl (meth)acrylate. Amide group-containing monomers: for example, (meth)acrylamide; N,N-dialkyl(meth)acrylamides such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(t-butyl)(meth)acrylamide; N-alkyl(meth)acrylamides such as N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, and Nn-butyl(meth)acrylamide; N-vinyl carboxylic acid amides such as N-vinylacetamide; monomers having a hydroxyl group and an amide group, for example, N-(2-hydroxyethyl)(meth)acrylamide; N-hydroxyalkyl (meth)acrylamide, such as N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, and N-(4-hydroxybutyl) (meth)acrylamide; monomers having an alkoxy group and an amide group, such as N-alkoxyalkyl (meth)acrylamide, such as N-methoxymethyl (meth)acrylamide, N-methoxyethyl (meth)acrylamide, and N-butoxymethyl (meth)acrylamide; and others, such as N,N-dimethylaminopropyl (meth)acrylamide. Aminoalkyl (meth)acrylates: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate. Alkoxy group-containing monomers: for example, alkoxyalkyl (meth)acrylates such as 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and ethoxypropyl (meth)acrylate; alkoxyalkylene (meth)acrylates such as methoxyethylene glycol (meth)acrylate and methoxypolypropylene glycol (meth)acrylate. Monomers containing a sulfonic acid group or a phosphoric acid group: for example, styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, sulfopropyl (meth)acrylate, (meth)acryloyloxynaphthalenesulfonic acid, 2-hydroxyethyl acryloyl phosphate, etc. (Meth)acrylic acid esters having an alicyclic hydrocarbon group: for example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and the like. (Meth)acrylic acid esters having an aromatic hydrocarbon group: for example, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, and the like. Vinyl ethers: for example, vinyl alkyl ethers such as methyl vinyl ether and ethyl vinyl ether. Vinyl esters: for example, vinyl acetate, vinyl propionate, etc. Aromatic vinyl compounds: for example, styrene, α-methylstyrene, vinyltoluene, etc. Olefins: For example, ethylene, butadiene, isoprene, isobutylene, etc. Other examples include heterocyclic ring-containing (meth)acrylates such as tetrahydrofurfuryl (meth)acrylate, halogen atom-containing (meth)acrylates such as vinyl chloride and fluorine atom-containing (meth)acrylates, silicon atom-containing (meth)acrylates such as silicone (meth)acrylate, and (meth)acrylic acid esters obtained from alcohols derived from terpene compounds.

[0054] When such a copolymerizable monomer is used, the amount of the copolymerizable monomer is not particularly limited, but is usually appropriate to be 0.01% by weight or more of the monomer raw material A. From the viewpoint of better exerting the effect of using the copolymerizable monomer, the amount of the copolymerizable monomer may be 0.1% by weight or more of the monomer raw material A, or may be 1% by weight or more. In some preferred embodiments, the content of the copolymerizable monomer in the monomer raw material A is 3% by weight or more, more preferably 5% by weight or more, and even more preferably 7% by weight or more (e.g., 8% by weight or more). The more the amount of the copolymerizable monomer used, the higher the cohesiveness and the more the bending recovery tend to improve. In addition, the amount of the copolymerizable monomer used can be 50% by weight or less of the monomer raw material A, and preferably 30% by weight or less. This can prevent the cohesive force of the adhesive from becoming too high, and can improve the tackiness at room temperature (25°C). In some preferred embodiments, the amount of the copolymerizable monomer used is 20% by weight or less of the monomer raw material A, more preferably 15% by weight or less (e.g., 12% by weight or less), and may be 10% by weight or less. By limiting the amount of copolymerizable monomer used, the cohesive strength of the adhesive is reduced, the elastic modulus (typically the surface elastic modulus) falls within a suitable range, making it easier to obtain excellent bending retention and increase the adhesive strength.

[0055] In some embodiments, the monomer raw material A may contain a monomer having a nitrogen atom-containing ring. By using a monomer having a nitrogen atom-containing ring, the cohesive strength and polarity of the adhesive can be adjusted, and the adhesive strength after heating can be suitably improved. By including a monomer having a nitrogen atom-containing ring in the monomer raw material A, the compatibility between the polymer (A) formed from the monomer raw material A and the polymer (B) tends to be improved. This makes it easier to obtain a reinforcing film that can greatly increase the adhesive strength by heating.

[0056] The monomer having a nitrogen atom-containing ring can be selected from the above examples, and can be used alone or in combination of two or more. In some embodiments, the monomer raw material A preferably contains at least one monomer selected from the group consisting of N-vinyl cyclic amides and cyclic amides having a (meth)acryloyl group as the monomer having a nitrogen atom-containing ring.

[0057] Specific examples of N-vinyl cyclic amides include N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, etc. Particularly preferred are N-vinyl-2-pyrrolidone and N-vinyl-2-caprolactam. Specific examples of cyclic amides having a (meth)acryloyl group include N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylmorpholine, etc. A suitable example is N-acryloylmorpholine (ACMO).

[0058] The amount of the monomer having a nitrogen atom-containing ring used is not particularly limited, and is usually 40% by weight or less of the monomer raw material A, and may be 30% by weight or less, 20% by weight or less, or 10% by weight or less. In some preferred embodiments, from the viewpoint of lowering the cohesive strength and lowering the elastic modulus (typically the surface elastic modulus), the content of the monomer having a nitrogen atom-containing ring in the monomer raw material A is 7% by weight or less, more preferably 5% by weight or less, and even more preferably 3% by weight or less (e.g., 1.5% by weight or less). In addition, the amount of the monomer having a nitrogen atom-containing ring used is usually 0.01% by weight or more of the monomer raw material A (preferably 0.1% by weight or more, for example 0.5% by weight or more). From the viewpoint of obtaining a suitable cohesive strength and elastic modulus, in some embodiments, the amount of the monomer having a nitrogen atom-containing ring used may be 0.8% by weight or more of the monomer raw material A, and may be 1.0% by weight or more.

[0059] In some preferred embodiments, the monomer raw material A includes a hydroxyl group-containing monomer. The use of the hydroxyl group-containing monomer adjusts the cohesive strength and polarity of the adhesive, and thus the elastic modulus (typically the surface elastic modulus), and the effects of the technology disclosed herein can be preferably realized. In addition, the hydroxyl group-containing monomer provides a reaction site with a crosslinking agent (e.g., an isocyanate-based crosslinking agent) described later, and can increase the cohesive strength of the adhesive through a crosslinking reaction.

[0060] As the hydroxyl group-containing monomer, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, N-(2-hydroxyethyl)(meth)acrylamide, etc. can be suitably used. Among them, preferred examples include 2-hydroxyethyl acrylate (HEA), 4-hydroxybutyl acrylate (4HBA), and N-(2-hydroxyethyl)acrylamide (HEAA). From the viewpoint of obtaining a cohesive force suitable for bending recovery and bending retention, 4HBA is particularly preferred.

[0061] The amount of the hydroxyl-containing monomer used is not particularly limited, and is usually appropriate to be 40% by weight or less of the monomer raw material A, may be 30% by weight or less, or may be 20% by weight or less. In some preferred embodiments, from the viewpoint of reducing the cohesive strength and thus the elastic modulus (typically the surface elastic modulus), the content of the hydroxyl-containing monomer in the monomer raw material A is 15% by weight or less, more preferably 12% by weight or less (e.g., 10% by weight or less). By limiting the amount of the hydroxyl-containing monomer used, the mobility of the polymer (B) in the adhesive layer is improved, and it is easy to realize an increase in adhesive strength. In some other embodiments, the content of the hydroxyl-containing monomer may be 5% by weight or less of the monomer raw material A. In addition, the amount of the hydroxyl-containing monomer used is appropriate to be 0.01% by weight or more of the monomer raw material A (preferably 0.1% by weight or more, for example 0.5% by weight or more). From the viewpoint of obtaining an appropriate cohesive strength and elastic modulus, in some preferred embodiments, the amount of the hydroxyl group-containing monomer used is 1 wt % or more of the monomer raw material A, more preferably 3 wt % or more, even more preferably 5 wt % or more, and particularly preferably 7 wt % or more (e.g., 8 wt % or more).

[0062] In some embodiments, a monomer having a nitrogen atom-containing ring and a hydroxyl group-containing monomer can be used in combination as a copolymerizable monomer. In this case, the total amount of the monomer having a nitrogen atom-containing ring and the hydroxyl group-containing monomer can be, for example, 0.1% by weight or more of the monomer raw material A, preferably 1% by weight or more, more preferably 3% by weight or more, even more preferably 5% by weight or more, particularly preferably 7% by weight or more (e.g., 9% by weight or more), and may be 10% by weight or more, 15% by weight or more, 20% by weight or more, or 25% by weight or more. In addition, the total amount of the monomer having a nitrogen atom-containing ring and the hydroxyl group-containing monomer can be, for example, 50% by weight or less of the monomer raw material A, and preferably 30% by weight or less. In some preferred embodiments, the total amount of the monomer having a nitrogen atom-containing ring and the hydroxyl group-containing monomer is 20% by weight or less of the monomer raw material A, more preferably 15% by weight or less (e.g., 12% by weight or less).

[0063] In an embodiment in which the monomer raw material A contains a combination of a monomer having a nitrogen atom-containing ring and a hydroxyl group-containing monomer, the content of the monomer having a nitrogen atom-containing ring in the monomer raw material A (W N ) and the content of hydroxyl group-containing monomers (W OH The relationship (weight basis) between W and W is not particularly limited. N / W OH may be, for example, 0.01 or more, and is usually 0.05 or more, may be 0.10 or more, or may be 0.12 or more. N / W OH may be, for example, 10 or less, and is usually suitably 1 or less, and is preferably 0.50 or less, or may be 0.30 or less, or may be 0.20 or less, or may be 0.15 or less.

[0064] In some embodiments, it is preferable that the monomer raw material A does not contain a monomer (monomer S1) having a polyorganosiloxane skeleton, which is preferably used as a constituent of the monomer raw material B described later, or that the content of the monomer is less than 10% by weight (more preferably less than 5% by weight, for example less than 2% by weight) of the monomer raw material A. With the monomer raw material A having such a composition, a reinforcing film that preferably achieves both initial reworkability and strong adhesion after the adhesion strength increases can be preferably realized. For the same reason, in some other embodiments, it is preferable that the monomer raw material A does not contain monomer S1, or if it contains monomer S1, its content (weight basis) is lower than the content of monomer S1 in the monomer raw material B.

[0065] The method for obtaining the polymer (A) is not particularly limited, and various polymerization methods such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization can be appropriately adopted. In some embodiments, the solution polymerization method can be preferably adopted. The polymerization temperature when carrying out the solution polymerization can be appropriately selected depending on the type of monomer and solvent used, the type of polymerization initiator, and the like, and can be, for example, about 20°C to 170°C (typically about 40°C to 140°C).

[0066] The initiator used for the polymerization can be appropriately selected from conventionally known thermal polymerization initiators, photopolymerization initiators, etc., depending on the polymerization method. The polymerization initiator can be used alone or in combination of two or more kinds.

[0067] Examples of the thermal polymerization initiator include azo-based polymerization initiators (e.g., 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 2,2'-azobis(2-methylpropionic acid) dimethyl, 4,4'-azobis-4-cyanovaleric acid, azobisisovaleronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2 -imidazolin-2-yl)propane]dihydrochloride, 2,2'-azobis(2-methylpropionamidine)disulfate, 2,2'-azobis(N,N'-dimethyleneisobutylamidine)dihydrochloride, etc.); persulfates such as potassium persulfate; peroxide-based polymerization initiators (e.g., dibenzoyl peroxide, t-butyl permaleate, lauroyl peroxide, etc.); redox-based polymerization initiators, etc. The amount of the thermal polymerization initiator used is not particularly limited, but can be, for example, within the range of 0.01 to 5 parts by weight, preferably 0.05 to 3 parts by weight, relative to 100 parts by weight of the monomer component (monomer raw material A) used in the preparation of the acrylic polymer.

[0068] The photopolymerization initiator is not particularly limited, but for example, a benzoin ether-based photopolymerization initiator, an acetophenone-based photopolymerization initiator, an α-ketol-based photopolymerization initiator, an aromatic sulfonyl chloride-based photopolymerization initiator, a photoactive oxime-based photopolymerization initiator, a benzoin-based photopolymerization initiator, a benzyl-based photopolymerization initiator, a benzophenone-based photopolymerization initiator, a ketal-based photopolymerization initiator, a thioxanthone-based photopolymerization initiator, an acylphosphine oxide-based photopolymerization initiator, etc. can be used. The amount of the photopolymerization initiator used is not particularly limited, but for example, it can be in the range of 0.01 to 5 parts by weight, preferably 0.05 to 3 parts by weight, relative to 100 parts by weight of the monomer raw material A.

[0069] In some embodiments, the polymer (A) may be included in the pressure-sensitive adhesive composition for forming the pressure-sensitive adhesive layer in the form of a partial polymer (polymer syrup) obtained by irradiating a mixture of the monomer raw material A and a polymerization initiator with ultraviolet (UV) light to polymerize a part of the monomer component. The pressure-sensitive adhesive composition containing such a polymer syrup can be applied to a predetermined substrate and irradiated with ultraviolet light to complete the polymerization. That is, the polymer syrup can be understood as a precursor of the polymer (A). The pressure-sensitive adhesive layer disclosed herein can be formed, for example, using a pressure-sensitive adhesive composition containing the polymer syrup and polymer (B).

[0070] (Polymer (B)) The polymer (B) in the technology disclosed herein is a polymer of a monomer component (monomer raw material B) containing a monomer having a polyorganosiloxane skeleton (hereinafter also referred to as "monomer S1") and a (meth)acrylic monomer. The polymer (B) can be said to be a copolymer of the monomer S1 and a (meth)acrylic monomer. The polymer (B) can be used alone or in combination of two or more. The polymer (B) can function as an adhesive strength increase retarder that suppresses the adhesive strength at the initial stage of application to an adherend due to the low polarity and mobility of the polyorganosiloxane structure derived from the monomer S1, and increases the adhesive strength to the adherend by heating. The monomer S1 is not particularly limited, and any monomer containing a polyorganosiloxane skeleton can be used. The monomer S1 promotes uneven distribution of the polymer (B) on the surface of the adhesive layer in the reinforcing film before use (before application to the adherend) due to the low polarity derived from its structure, and exhibits light peelability (low adhesiveness) at the initial stage of application. As the monomer S1, a structure having a polymerizable reactive group at one end can be preferably used. According to a configuration including such a monomer S1 unit and a (meth)acrylic monomer unit, a polymer (B) having a polyorganosiloxane skeleton in a side chain is formed. The polymer (B) having such a structure is likely to have a low initial adhesive strength and a high adhesive strength after heating due to the mobility and ease of movement of the side chain. In some embodiments, the monomer S1 is preferably one having a polymerizable reactive group at one end and not having a functional group at the other end that causes a crosslinking reaction with the polymer (A). The polymer (B) in which the monomer S1 having such a structure is copolymerized is likely to have a low initial adhesive strength and a high adhesive strength after heating due to the mobility of the polyorganosiloxane structure derived from the monomer S1.

[0071] As the monomer S1, for example, a compound represented by the following general formula (1) or (2) can be used. More specifically, examples of the silicone oil having a reactive end, manufactured by Shin-Etsu Chemical Co., Ltd., include X-22-174ASX, X-22-2426, X-22-2475, and KF-2012. The monomer S1 can be used alone or in combination of two or more. [ka] [ka] Here, R in the above general formulas (1) and (2) 3 is hydrogen or methyl, and R 4 is a methyl group or a monovalent organic group, and m and n are integers of 0 or greater.

[0072] The functional group equivalent of the monomer S1 can be an appropriate value within a range where the desired effect is achieved by using the monomer S1, and is not limited to a specific range. From the viewpoint of sufficiently suppressing the initial adhesive strength, the functional group equivalent is, for example, 100 g / mol or more, or 200 g / mol or more, and is suitably 300 g / mol or more (for example, 500 g / mol or more), preferably 800 g / mol or more, and more preferably 1500 g / mol or more. In a particularly preferred embodiment, from the viewpoint of achieving both low adhesive strength at the initial stage of application and increased adhesive strength after heating, the functional group equivalent is 2000 g / mol or more, more particularly preferably 2500 g / mol or more, may be 3000 g / mol or more, 4000 g / mol or more, or may be 5000 g / mol or more. In some other embodiments, the functional group equivalent may be 9000 g / mol or more, may be 12000 g / mol or more, or may be 15000 g / mol or more.

[0073] From the viewpoint of sufficiently increasing the adhesive strength, the functional group equivalent is, for example, suitably 30000 g / mol or less, may be 20000 g / mol or less, may be less than 15000 g / mol, or may be less than 10000 g / mol. In some preferred embodiments, the functional group equivalent of the monomer S1 is 7000 g / mol or less, more preferably 5500 g / mol or less, even more preferably 4500 g / mol or less, may be 4200 g / mol or less, or may be 3500 g / mol or less. When the functional group equivalent of the monomer S1 is within the above range, the compatibility (for example, compatibility with the base polymer) in the adhesive layer is likely to be good, the mobility of the polyorganosiloxane skeleton (chain) of the polymer (B) is good, and the mobility of the polymer (B) is easily adjusted to an appropriate range, making it easier to realize an adhesive layer that is compatible with both initial low adhesion and increased adhesive strength after heating.

[0074] Here, the term "functional group equivalent" refers to the weight of the main skeleton (e.g., polydimethylsiloxane) bound to one functional group. The unit g / mol is calculated based on 1 mol of functional group. The functional group equivalent of the monomer S1 can be calculated, for example, based on nuclear magnetic resonance (NMR). 1 It can be calculated from the H-NMR (proton NMR) spectrum intensity. 1 The functional group equivalent weight (g / mol) of monomer S1 was calculated based on the H-NMR spectrum intensity as follows: 1 This can be done based on a general structural analysis method related to H-NMR spectrum analysis, and if necessary, by referring to the description in Japanese Patent No. 5951153. In the functional group equivalent of the monomer S1, the functional group means a polymerizable functional group (for example, an ethylenically unsaturated group such as a (meth)acryloyl group, a vinyl group, or an allyl group).

[0075] In addition, when two or more kinds of monomers having different functional group equivalents are used as the monomer S1, the functional group equivalent of the monomer S1 can be an arithmetic average value. 1 , Monomer S1 2 Monomer S1 nThe functional group equivalent of the monomer S1 consisting of (a) can be calculated by the following formula. Functional group equivalent of monomer S1 (g / mol) = (monomer S1 1 Functional group equivalent weight × monomer S1 1 + Monomer S1 2 Functional group equivalent weight × monomer S1 2 + + Monomer S1 n Functional group equivalent weight × monomer S1 n (amount of monomer S1) / (amount of monomer S1 1 + Monomer S1 2 + + Monomer S1 n (amount of mixture)

[0076] The content of the monomer S1 can be an appropriate value within a range in which the desired effect is achieved using the monomer S1, and is not limited to a specific range. From the viewpoint of sufficiently suppressing the initial adhesive strength, in some embodiments, the content of the monomer S1 in the total amount of the monomer components (monomer raw material B) for preparing the polymer (B) may be, for example, 5% by weight or more, and from the viewpoint of better exerting the effect as an adhesive strength increase retarder, it is preferably 10% by weight or more, more preferably 12% by weight or more, even more preferably 15% by weight or more, particularly preferably 18% by weight or more, and may be 20% by weight or more. In addition, from the viewpoint of polymerization reactivity and compatibility, the content of the monomer S1 in the monomer raw material B may be, for example, 80% by weight or less, and it is appropriate to set it to 60% by weight or less, preferably 50% by weight or less, more preferably 40% by weight or less, and even more preferably 30% by weight or less. By setting the polymerization ratio of the monomer S1 within an appropriate range, the increase in adhesive strength can be suitably expressed.

[0077] The monomer raw material B contains, in addition to the monomer S1, a (meth)acrylic monomer copolymerizable with the monomer S1. By using one or more (meth)acrylic monomers, the mobility of the polymer (B) in the adhesive layer can be suitably adjusted. This can also be useful for improving the compatibility between the polymer (B) and the polymer (A). The polymer (B) containing a (meth)acrylic monomer unit can be well compatible with the acrylic polymer, and therefore, by improving the mobility of the polymer (B) in the adhesive layer, it is easy to reduce the initial adhesive strength and improve the adhesive strength after heating.

[0078] In the polymer (B) used in the technology disclosed herein, the composition of the (meth)acrylic monomer contained in the monomer raw material B is such that the glass transition temperature T B1 is the glass transition temperature T of polymer (A). A It is preferable that the temperature is set higher than T B1 can be set to be higher than 0° C., for example. Here, the glass transition temperature T B1 means the Tg calculated by the Fox formula based on the composition of only the (meth)acrylic monomer among the monomer components used in the preparation of the polymer (B). B1 The glass transition temperature T can be calculated from the glass transition temperature of the homopolymer of each (meth)acrylic monomer and the weight fraction of each (meth)acrylic monomer in the total amount of the (meth)acrylic monomers by applying the above-mentioned Fox formula to only the (meth)acrylic monomers among the monomer components used in the preparation of the polymer (B). B1 The initial adhesive strength is easily suppressed by the polymer (B) having a relatively high glass transition temperature T B1 A polymer (B) having a relatively high T (typically higher than 0° C.) tends to provide a reinforcing film with a large adhesion increase ratio.

[0079] In some preferred embodiments, T B1is 10° C. or higher, more preferably 30° C. or higher, further preferably 40° C. or higher, and may be 45° C. or higher. B1 As the temperature increases, the initial adhesive strength tends to be better suppressed. B1 It is considered that, when the polymer (B) has a temperature of at least a predetermined temperature, the increase in the mobility and movement of the polyorganosiloxane structural portion that accompanies an increase in temperature to room temperature or to a region somewhat higher than room temperature is effectively suppressed by the monomer units derived from the (meth)acrylic monomer contained in the polymer (B), and the low adhesion caused by the presence of the polyorganosiloxane structural portion can be better maintained. From the viewpoint of more stably maintaining the low adhesion at the initial stage of application, in some embodiments, T B1 may be, for example, 50° C. or more, 55° C. or more, or 60° C. or more. B1 For example, T may be 120° C. or less, or may be 100° C. or less. B1 When T is low, the adhesive strength tends to increase more easily by heating. B1 is, for example, 90° C. or less, more preferably 70° C. or less, further preferably 60° C. or less, and particularly preferably 55° C. or less (for example, 50° C. or less).

[0080] T B1 From the viewpoint of easily exerting the effect of appropriately setting, the total amount of monomer S1 and the (meth)acrylic monomer in all monomer components for preparing polymer (B) may be, for example, 50% by weight or more, 70% by weight or more, 85% by weight or more, 90% by weight or more, 95% by weight or more, or substantially 100% by weight.

[0081] Glass transition temperature T of polymer (B) B is not particularly limited and can be selected so as to obtain preferred properties in the reinforcing film disclosed herein. B may be, for example, less than 50° C., 30° C. or less, 20° C. or less, 15° C. or less, or 10° C. or less.B When the T of the polymer (B) is lowered, the mobility (typically temperature-sensitive mobility) of the polymer (B) is improved, and the adhesive strength can be significantly increased. In some preferred embodiments, the T of the polymer (B) B is 5° C. or less, may be less than 0° C., may be −5° C. or less, or may be −10° C. or less. In some embodiments, the T B may be, for example, −40° C. or higher, or −30° C. or higher. B The higher the T of the polymer (B), the more the polymer (B) unevenly distributed on the surface side of the pressure-sensitive adhesive layer when attached to an adherend contributes to a decrease in the initial adhesive strength, and the more the adhesive layer tends to have excellent easy peelability at the initial stage of attachment. B is -20°C or higher, and may be -15°C or higher. B By setting this within an appropriate range, it is possible to control the easy peelability at the initial stage of application and the increase in adhesive strength after heating within preferred ranges.

[0082] In some embodiments, the composition of the monomer components for preparing the polymer (B) is T B1 T B To be higher, i.e. T B1 -T B can be set to be greater than 0° C. With such a composition, the effect of adjusting the mobility of the polymer (B) by the composition of the (meth)acrylic monomer contained in the monomer component is easily exhibited. B1 -T B For example, T may be about 40° C. to 100° C., or about 50° C. to 90° C. In some preferred embodiments, T B1 -T B is 45° C. or more, more preferably 50° C. or more, and even more preferably 55° C. or more (for example, 58° C. or more). B1 -T B is preferably 80° C. or less, more preferably 70° C. or less, and further preferably 65° C. or less (for example, 62° C. or less).

[0083] From the viewpoint of facilitating control of the mobility of the polymer (B) in the pressure-sensitive adhesive layer, in some embodiments, the composition of the monomer components for preparing the polymer (B) is selected from the group consisting of a monomer having a glass transition temperature T A In relation to T B T A 20°C higher than T B -T A In some preferred embodiments, T B -T A is, for example, 30° C. or higher, more preferably 40° C. or higher, and even more preferably 50° C. or higher, and may be 60° C. or higher, or may be 70° C. or higher. B -T A For example, the temperature may be 130°C or less, 120°C or less, preferably 100°C or less, more preferably 80°C or less, and even more preferably 65°C or less, may be 55°C or less, or may be 45°C or less.

[0084] Examples of (meth)acrylic monomers that can be used for monomer raw material B include (meth)acrylic acid alkyl esters. The term "alkyl" as used herein refers to chain-like (including linear and branched) alkyl (groups) and does not include alicyclic hydrocarbon groups, which will be described later. For example, one or more of the monomers exemplified above as (meth)acrylic acid alkyl esters that can be used for polymer (A) can be used as constituents of monomer raw material B. In some embodiments, monomer raw material B is (meth)acrylic acid C. 4-12 Alkyl ester (preferably (meth)acrylic acid C 4-10 Alkyl esters, such as (meth)acrylic acid C 6-10 In some other embodiments, the monomer feedstock B may contain at least one of methacrylic acid C 1-18 Alkyl ester (preferably methacrylic acid C 1-14 Alkyl esters, such as methacrylic acid C 1-10The monomer raw material B may contain at least one (meth)acrylic monomer selected from, for example, MMA, n-butyl methacrylate (BMA), and 2-ethylhexyl methacrylate (2EHMA).

[0085] Other examples of the (meth)acrylic monomer include (meth)acrylic acid esters having an alicyclic hydrocarbon group. For example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, etc. can be used. In some embodiments, the monomer raw material B can contain at least one selected from dicyclopentanyl methacrylate, isobornyl methacrylate, and cyclohexyl methacrylate as the (meth)acrylic monomer.

[0086] The content of the (meth)acrylic acid alkyl ester and the (meth)acrylic acid ester having an alicyclic hydrocarbon group in the monomer raw material B may be, for example, 10% by weight or more and 95% by weight or less, 20% by weight or more and 95% by weight or less, 30% by weight or more and 90% by weight or less, 40% by weight or more and 90% by weight or less, or 50% by weight or more and 85% by weight or less. From the viewpoint of the ease of increasing the adhesive strength by heating, the use of the (meth)acrylic acid alkyl ester may be advantageous. In some embodiments, the content of the (meth)acrylic acid ester having an alicyclic hydrocarbon group may be less than 50% by weight, less than 30% by weight, less than 15% by weight, less than 10% by weight, or less than 5% by weight of the monomer raw material B. The (meth)acrylic acid ester having an alicyclic hydrocarbon group may not be used.

[0087] In some preferred embodiments, the (meth)acrylic monomer, which is a component of the monomer raw material B, may contain a monomer M2 having a homopolymer Tg of 50° C. or more. In the polymer (B), the monomer S1 and the monomer M2 are copolymerized to suitably control the mobility and mobility of the polyorganosiloxane structure portion with increasing temperature, and it is easy to achieve both initial easy peelability (reworkability) and increased adhesive strength after heating. In some embodiments, the Tg of the homopolymer of the monomer M2 may be 60° C. or more, 70° C. or more, 80° C. or more, or 90° C. or more. In addition, the upper limit of the Tg of the homopolymer of the monomer M2 is not particularly limited, but from the viewpoint of ease of synthesis of the polymer (B), it is usually appropriate that it is 200° C. or less. In some embodiments, the Tg of the homopolymer of the monomer M2 may be, for example, 180° C. or less, 150° C. or less, or 120° C. or less.

[0088] As the monomer M2, for example, from among the (meth)acrylic monomers exemplified above, those that satisfy the conditions of Tg of the homopolymer can be used. For example, one or more monomers selected from the group consisting of (meth)acrylic acid alkyl esters and (meth)acrylic acid esters having an alicyclic hydrocarbon group can be used. As the (meth)acrylic acid alkyl ester, a methacrylic acid alkyl ester having an alkyl group with 1 to 4 carbon atoms can be preferably used.

[0089] In an embodiment in which the monomer raw material B contains the monomer M2, the content of the monomer M2 may be, for example, 5% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, or 30% by weight or more of the monomer raw material B. In some embodiments, the content of the monomer M2 may be 35% by weight or more, 40% by weight or more, 45% by weight or more, 50% by weight or more, or 55% by weight or more of the monomer raw material B. In addition, the content of the monomer M2 may be, for example, 90% by weight or less, and is usually suitably 80% by weight or less, preferably 75% by weight or less, may be 70% by weight or less, or may be 65% by weight or less. In some preferred embodiments, the content of the monomer M2 is 60% by weight or less (for example, 50% by weight or less, typically 42% by weight or less). In polymer (B), the copolymerization ratio of monomer M2 having a Tg of 50° C. or higher is limited to a predetermined value or less, so that an increase in adhesive strength after heating can be preferably achieved based on the mobility of polymer (B) at around 50° C. From the same viewpoint, the content of monomer M2 in monomer raw material B may be 35% by weight or less, 25% by weight or less, or 15% by weight or less (e.g., 5% by weight or less).

[0090] The content of the monomer M2 can be preferably applied, for example, to an embodiment in which the monomer M2 is composed of one or more monomers selected from the group consisting of (meth)acrylic acid alkyl esters and the (meth)acrylic acid esters having an alicyclic hydrocarbon group, or an embodiment in which the monomer M2 is composed of one or more monomers selected from (meth)acrylic acid alkyl esters (e.g., methacrylic acid alkyl esters). One preferred example of such an embodiment is an embodiment in which the monomer M2 is composed of MMA.

[0091] In some embodiments, the (meth)acrylic monomer may contain a monomer M3 having a homopolymer Tg of less than 50° C. (typically, −20° C. or more and less than 50° C.). By using the monomer M3, it becomes easier to obtain a reinforcing film that has a good balance between adhesive strength and cohesive strength after the adhesive strength is increased. From the viewpoint of easily exerting such an effect, it is preferable to use the monomer M3 in combination with the monomer M2.

[0092] As the monomer M3, for example, one having a homopolymer Tg that satisfies the conditions can be used from among the (meth)acrylic monomers exemplified above. For example, one or more monomers selected from the group consisting of (meth)acrylic acid alkyl esters can be used.

[0093] In an embodiment in which the monomer raw material B contains the monomer M3, the content of the monomer M3 may be, for example, 5% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, or 35% by weight or more of the monomer raw material B. The content of the monomer M3 is usually suitably 70% by weight or less, 60% by weight or less, or 50% by weight or less of the monomer raw material B. The above content of the monomer M3 can be preferably applied, for example, to an embodiment in which the monomer M3 is composed of one or more monomers selected from (meth)acrylic acid alkyl esters (e.g., methacrylic acid alkyl esters).

[0094] In some embodiments of the reinforcing film disclosed herein, the monomer raw material B preferably contains 30% by weight or less of a monomer having a homopolymer Tg higher than 170°C. Here, unless otherwise specified, the monomer content of X% by weight or less in this specification is a concept including an embodiment in which the content of the monomer is 0% by weight, that is, an embodiment in which the monomer is not substantially contained. In addition, "substantially not contained" means that the monomer is not used at least intentionally. When the copolymerization ratio of a monomer having a homopolymer Tg higher than 170°C is high, the mobility of the polymer (B) tends to be insufficient, and it may be difficult to increase the adhesive strength by heating to a temperature range higher than 50°C.

[0095] In some embodiments, the monomer raw material B preferably contains at least MMA as a (meth)acrylic monomer. A polymer (B) in which MMA is copolymerized can easily produce a reinforcing film with high adhesive strength after heating. The proportion of MMA in the total amount of (meth)acrylic monomers contained in the monomer raw material B may be, for example, 5% by weight or more, 10% by weight or more, 20% by weight or more, 30% by weight or more, or 40% by weight or more. In addition, the proportion of MMA in the total amount of the monomer raw material B is usually appropriate to be 95% by weight or less, and in some preferred embodiments, the proportion of MMA in the total amount of the monomer raw material B may be 75% by weight or less, 65% by weight or less, 60% by weight or less, or 55% by weight or less (for example, 50% by weight or less) from the viewpoint of increasing adhesive strength after heating.

[0096] Other examples of monomers that may be included together with monomer S1 as a monomer unit constituting polymer (B) include the carboxyl group-containing monomers, acid anhydride group-containing monomers, hydroxyl group-containing monomers, epoxy group-containing monomers, cyano group-containing monomers, isocyanate group-containing monomers, amide group-containing monomers, monomers having a nitrogen atom-containing ring (N-vinyl cyclic amides, cyclic amides having a (meth)acryloyl group, monomers having a succinimide skeleton, maleimides, itaconimides, etc.), aminoalkyl (meth)acrylates, vinyl esters, vinyl ethers, olefins, (meth)acrylic acid esters having an aromatic hydrocarbon group, heterocyclic ring-containing (meth)acrylates, halogen atom-containing (meth)acrylates, and (meth)acrylic acid esters obtained from terpene compound derivative alcohols, etc.

[0097] Further examples of monomers that may be contained together with the monomer S1 as a monomer unit constituting the polymer (B) include oxyalkylene di(meth)acrylates such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate; monomers having a polyoxyalkylene skeleton, such as polyethylene glycol and polypropylene glycol, having a polymerizable functional group such as a (meth)acryloyl group, a vinyl group, or an allyl group at one end of the polyoxyalkylene chain and an ether structure (alkyl ether, aryl ether, aryl alkyl ether, or the like) at the other end; methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, and propoxyethyl (meth)acrylate. alkoxyalkyl (meth)acrylates such as butoxyethyl (meth)acrylate and ethoxypropyl (meth)acrylate; salts such as alkali metal (meth)acrylate; polyvalent (meth)acrylates such as trimethylolpropane tri(meth)acrylate; halogenated vinyl compounds such as vinylidene chloride and 2-chloroethyl (meth)acrylate; oxazoline group-containing monomers such as 2-vinyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline and 2-isopropenyl-2-oxazoline; aziridine group-containing monomers such as (meth)acryloylaziridine and 2-aziridinylethyl (meth)acrylate; hydroxyl group-containing vinyl monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate and adducts of lactones and 2-hydroxyethyl (meth)acrylate; fluorine-containing vinyl monomers such as fluorine-substituted (meth)acrylic acid alkyl esters; reactive halogen-containing vinyl monomers such as 2-chloroethyl vinyl ether and vinyl monochloroacetate;Examples of the vinyl monomer include organosilicon-containing vinyl monomers such as vinyltrimethoxysilane, γ-(meth)acryloxypropyltrimethoxysilane, allyltrimethoxysilane, trimethoxysilylpropylallylamine, and 2-methoxyethoxytrimethoxysilane; and macromonomers having a radical polymerizable vinyl group at the monomer end obtained by polymerizing a vinyl group. These may be copolymerized with monomer S1 either alone or in combination of two or more.

[0098] In some embodiments, the polymer (B) may preferably be one that does not have a functional group that undergoes a crosslinking reaction with the polymer (A). In other words, the polymer (B) is preferably included in the adhesive layer in a form that is not chemically bonded to the polymer (A). The adhesive layer containing the polymer (B) in such a form has good mobility of the polymer (B) when heated, and is suitable for improving the adhesive strength increase ratio. The functional group that undergoes a crosslinking reaction with the polymer (A) may vary depending on the type of functional group possessed by the polymer (A), and may be, for example, an epoxy group, an isocyanate group, a carboxy group, an alkoxysilyl group, an amino group, etc.

[0099] The Mw of the polymer (B) is not particularly limited. The Mw of the polymer (B) may be, for example, 1000 or more, or 5000 or more. In some preferred embodiments, the Mw of the polymer (B) is 10,000 or more, more preferably 12,000 or more, 15,000 or more, 20,000 or more, 22,000 or more, or 25,000 or more, from the viewpoint of favorably exhibiting an increase in adhesive strength after heating. In some other embodiments, the Mw of the polymer (B) may be 30,000 or more, 50,000 or more, or 70,000 or more. The upper limit of the Mw of the polymer (B) is, for example, 500,000 or less, 350,000 or less, 200,000 or less, or 150,000 or less. From the viewpoint of adjusting the compatibility and mobility within the adhesive layer within an appropriate range and suitably exhibiting low adhesion at the initial stage of application, in some preferred embodiments, the Mw of the polymer (B) is 100,000 or less, more preferably 80,000 or less, even more preferably 60,000 or less, particularly preferably 40,000 or less (e.g., 30,000 or less), and may be 25,000 or less, or may even be 20,000 or less. By setting the Mw of the polymer (B) within an appropriate range, it is easy to obtain an adhesive that is excellent in both easy peelability and adhesive strength increase at the initial stage of application.

[0100] In some preferred embodiments, the Mw of the polymer (B) is preferably lower than the Mw of the polymer (A). This makes it easier to realize a reinforcing film that has both good reworkability at the initial stage of application and an increase in adhesive strength after heating. In some embodiments, the Mw of the polymer (B) may be, for example, 0.8 times or less, 0.75 times or less, 0.5 times or less, or 0.3 times or less of the Mw of the polymer (A). In some preferred embodiments, the Mw of the polymer (A) may be, for example, 0.8 times or less, 0.75 times or less, 0.5 times or less, or 0.3 times or less. A Mw of polymer (B) B Ratio (Mw B / Mw A ) is 0.3 or less, more preferably 0.2 or less, even more preferably 0.1 or less, and particularly preferably 0.06 or less (e.g., 0.05 or less). B / MwA ) is, for example, suitably 0.010 or more, preferably 0.020 or more, more preferably 0.03 or more, and even more preferably 0.04 or more. By setting the Mw of polymer (A) and the Mw of polymer (B) within an appropriate range, the effects of the technology disclosed herein can be better realized. In some other embodiments, the Mw of polymer (B) may be 0.03 times or less (e.g., 0.02 times or less) the Mw of polymer (A).

[0101] The polymer (B) can be prepared, for example, by polymerizing the above-mentioned monomers by a known method such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, or photopolymerization.

[0102] In order to adjust the molecular weight of the polymer (B), a chain transfer agent can be used as necessary. Examples of the chain transfer agent to be used include compounds having a mercapto group such as octyl mercaptan, lauryl mercaptan, t-nonyl mercaptan, t-dodecyl mercaptan, mercaptoethanol, and α-thioglycerol; thioglycolic acid, methyl thioglycolate, ethyl thioglycolate, propyl thioglycolate, butyl thioglycolate, t-butyl thioglycolate, 2-ethylhexyl thioglycolate, octyl thioglycolate, isooctyl thioglycolate, decyl thioglycolate, dodecyl thioglycolate, thioglycolic acid esters such as ethylene glycol thioglycolic acid ester, neopentyl glycol thioglycolic acid ester, and pentaerythritol thioglycolic acid ester; and α-methylstyrene dimer.

[0103] The amount of the chain transfer agent is not particularly limited, but is usually 0.05 to 20 parts by weight, preferably 0.1 to 15 parts by weight, and more preferably 0.2 to 10 parts by weight, per 100 parts by weight of the monomer. By adjusting the amount of the chain transfer agent added in this manner, a polymer (B) having a suitable molecular weight can be obtained. The chain transfer agent can be used alone or in combination of two or more kinds.

[0104] As a means for adjusting the molecular weight of the polymer (B), various conventionally known means including the use of the chain transfer agent can be used alone or in appropriate combination. The same applies to the molecular weight of the polymer (A). Non-limiting examples of such means include selection of a polymerization method, selection of the type and amount of a polymerization initiator, selection of a polymerization temperature, selection of the type and amount of a polymerization solvent in a solution polymerization method, selection of light irradiation intensity in a photopolymerization method, etc. A person skilled in the art can understand how to obtain a polymer having a desired molecular weight based on the description of the present specification including the specific examples described below and the common general technical knowledge at the time of filing of the present application.

[0105] In the reinforcing film disclosed herein, the amount of polymer (B) used relative to 100 parts by weight of polymer (A) can be, for example, 0.1 parts by weight or more, and from the viewpoint of obtaining a higher effect (preferably, light peelability at the initial stage of application), 0.5 parts by weight or more is preferable, 1 part by weight or more is more preferable, 1.5 parts by weight or more is even more preferable, and it may be 2 parts by weight or more. In some embodiments, from the viewpoint of improving reworkability, etc., the amount of polymer (B) used can be, for example, 3 parts by weight or more, may be 4 parts by weight or more, or may be 5 parts by weight or more. In addition, the amount of polymer (B) used relative to 100 parts by weight of polymer (A) may be, for example, 75 parts by weight or less, may be 30 parts by weight or less, may be 10 parts by weight or less, or may be 8 parts by weight or less. From the viewpoint of suitably realizing the desired increase in adhesive strength, in some preferred embodiments, the amount of polymer (B) used relative to 100 parts by weight of polymer (A) is 5 parts by weight or less, more preferably 4 parts by weight or less, even more preferably 3 parts by weight or less, and particularly preferably 2.5 parts by weight or less. In some other preferred embodiments, the amount of polymer (B) used per 100 parts by weight of polymer (A) is 1.5 parts by weight or less (for example, 1.2 parts by weight or less). By setting the amount of polymer (B) used within the above range, it is easy to achieve good bending recovery and bending retention. In addition, it is possible to better achieve both easy peeling property at the initial stage of application and increase in adhesive strength.

[0106] The pressure-sensitive adhesive layer may contain a polymer (optional polymer) other than the polymer (A) and the polymer (B) as necessary, as long as the performance of the reinforcing film disclosed herein is not significantly impaired. The amount of such an optional polymer used is usually 20% by weight or less of the total polymer components contained in the pressure-sensitive adhesive layer, and may be 15% by weight or less, or 10% by weight or less. In some embodiments, the amount of the optional polymer used may be 5% by weight or less, 3% by weight or less, or 1% by weight or less of the total polymer components. The pressure-sensitive adhesive layer may be substantially free of polymers other than the polymer (A) and the polymer (B).

[0107] (Crosslinking agent) In the pressure-sensitive adhesive layer, a crosslinking agent may be used as necessary for the purpose of adjusting the cohesive force. As the crosslinking agent, a crosslinking agent known in the field of pressure-sensitive adhesives may be used, and examples thereof include epoxy-based crosslinking agents, isocyanate-based crosslinking agents, silicone-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, silane-based crosslinking agents, alkyl etherified melamine-based crosslinking agents, and metal chelate-based crosslinking agents. Isocyanate-based crosslinking agents, epoxy-based crosslinking agents, and metal chelate-based crosslinking agents can be preferably used. As a crosslinking agent that satisfies both bending recovery and bending retention, an isocyanate-based crosslinking agent can be preferably used. The crosslinking agent may be used alone or in combination of two or more.

[0108] As the isocyanate-based crosslinking agent, a polyfunctional isocyanate (which refers to a compound having an average of two or more isocyanate groups per molecule, including those having an isocyanurate structure) can be preferably used. The isocyanate-based crosslinking agent can be used alone or in combination of two or more kinds.

[0109] Examples of the polyfunctional isocyanate include aliphatic polyisocyanates, alicyclic polyisocyanates, and aromatic polyisocyanates. Specific examples of aliphatic polyisocyanates include 1,2-ethylene diisocyanate; tetramethylene diisocyanates such as 1,2-tetramethylene diisocyanate, 1,3-tetramethylene diisocyanate, and 1,4-tetramethylene diisocyanate; hexamethylene diisocyanates such as 1,2-hexamethylene diisocyanate, 1,3-hexamethylene diisocyanate, 1,4-hexamethylene diisocyanate, 1,5-hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, and 2,5-hexamethylene diisocyanate; 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, and lysine diisocyanate.

[0110] Specific examples of alicyclic polyisocyanates include isophorone diisocyanate; cyclohexyl diisocyanates such as 1,2-cyclohexyl diisocyanate, 1,3-cyclohexyl diisocyanate, and 1,4-cyclohexyl diisocyanate; cyclopentyl diisocyanates such as 1,2-cyclopentyl diisocyanate and 1,3-cyclopentyl diisocyanate; hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated tetramethylxylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

[0111] Specific examples of aromatic polyisocyanates include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylether diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, Examples of the diisocyanate include 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, naphthylene-1,4-diisocyanate, naphthylene-1,5-diisocyanate, 3,3'-dimethoxydiphenyl-4,4'-diisocyanate, xylylene-1,4-diisocyanate, and xylylene-1,3-diisocyanate.

[0112] A preferred example of the polyfunctional isocyanate is a polyfunctional isocyanate having an average of three or more isocyanate groups per molecule. Such a trifunctional or higher isocyanate may be a multimer (e.g., a dimer or trimer) of a bifunctional or trifunctional or higher isocyanate, a derivative (e.g., an addition reaction product of a polyhydric alcohol and two or more molecules of a polyfunctional isocyanate), a polymer, or the like. Examples of the isocyanate include a dimer or trimer of diphenylmethane diisocyanate, an isocyanurate of hexamethylene diisocyanate (a trimer adduct of an isocyanurate structure), a reaction product of trimethylolpropane and tolylene diisocyanate, a reaction product of trimethylolpropane and hexamethylene diisocyanate, a trimethylolpropane adduct of xylylene diisocyanate, a trimethylolpropane adduct of isophorone diisocyanate, a trimethylolpropane adduct of hexamethylene diisocyanate, polymethylene polyphenylisocyanate, polyether polyisocyanate, polyester polyisocyanate, and adducts of these with various polyols, and polyfunctional isocyanates such as polyisocyanates multifunctionalized with an isocyanurate bond, a biuret bond, an allophanate bond, or the like.

[0113] Commercially available products of the above-mentioned polyfunctional isocyanates include those manufactured by Asahi Kasei Chemicals Corporation under the trade name "Duranate TPA-100," those manufactured by Tosoh Corporation under the trade names "Coronate L," "Coronate HL," "Coronate HK," "Coronate HX," and "Coronate 2096," and those manufactured by Mitsui Chemicals, Inc. under the trade names "Takenate D110N," "Takenate D120N," "Takenate D140N," and "Takenate D160N."

[0114] Examples of epoxy crosslinking agents include bisphenol A, epichlorohydrin type epoxy resins, ethylene glycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol glycidyl ether, trimethylolpropane triglycidyl ether, diglycidylaniline, diamine glycidylamine, N,N,N',N'-tetraglycidyl-m-xylylenediamine, and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, etc. These may be used alone or in combination of two or more.

[0115] Examples of the metal chelate compound include metal components such as aluminum, iron, tin, titanium, nickel, etc., and chelate components such as acetylene, methyl acetoacetate, ethyl lactate, etc. These may be used alone or in combination of two or more.

[0116] The amount of the crosslinking agent used is not particularly limited, and may be, for example, more than 0 parts by weight relative to 100 parts by weight of the polymer (A). The amount of the crosslinking agent used may be, for example, 0.01 parts by weight or more relative to 100 parts by weight of the polymer (A), and is preferably 0.05 parts by weight or more. By increasing the amount of the crosslinking agent used, the adhesive strength at the initial stage of application is suppressed, and reworkability tends to improve. The bending recovery and processability tend to be excellent. In some embodiments, the amount of the crosslinking agent used relative to 100 parts by weight of the polymer (A) may be 0.1 parts by weight or more, 0.5 parts by weight or more, or 0.8 parts by weight or more. On the other hand, from the viewpoint of obtaining an increase in adhesive strength after heating while allowing the mobility of the polymer (B) to an appropriate extent, the amount of the crosslinking agent used relative to 100 parts by weight of the polymer (A) is usually appropriately 15 parts by weight or less, may be 10 parts by weight or less, or may be 5 parts by weight or less.

[0117] The technology disclosed herein can be preferably implemented in an embodiment using at least an isocyanate-based crosslinking agent as a crosslinking agent. From the viewpoint of achieving both good reworkability at the initial stage of application and increased adhesive strength after heating, in some embodiments, the amount of the isocyanate-based crosslinking agent used relative to 100 parts by weight of the polymer (A) can be, for example, 0.01 parts by weight or more, preferably 0.05 parts by weight or more, more preferably 0.07 parts by weight or more, and may be 0.10 parts by weight or more, or may be 0.15 parts by weight or more (for example, 0.20 parts by weight or more). By increasing the amount of the isocyanate-based crosslinking agent used, moderate cohesive strength and elastic modulus are obtained, and bending recovery and processability tend to be excellent. In addition, the amount of the isocyanate-based crosslinking agent used relative to 100 parts by weight of the polymer (A) can be, for example, 5 parts by weight or less, preferably less than 1.0 parts by weight, more preferably less than 0.5 parts by weight, even more preferably less than 0.3 parts by weight, and particularly preferably less than 0.2 parts by weight (for example, 0.15 parts by weight or less). This appropriately reduces the cohesive strength of the adhesive and, in turn, the modulus of elasticity (typically, the surface modulus of elasticity), resulting in good bending retention and also making it easier to obtain an increase in adhesive strength after heating.

[0118] Although not particularly limited, when an isocyanate-based crosslinking agent is used in a configuration in which the pressure-sensitive adhesive layer contains a hydroxyl group-containing monomer as a monomer unit, the molar ratio ([NCO] / [OH]) of the isocyanate group and the hydroxyl group contained in the pressure-sensitive adhesive layer can be, for example, 0.001 or more. By increasing the amount of the isocyanate-based crosslinking agent used relative to the hydroxyl group-containing monomer in this way, the elastic modulus (typically the surface elastic modulus) of the pressure-sensitive adhesive becomes in a suitable range, and the bending recovery tends to be improved. In addition, the processability also tends to be excellent. In some preferred embodiments, the molar ratio ([NCO] / [OH]) is 0.002 or more, more preferably 0.004 or more, even more preferably 0.006 or more (for example, 0.007 or more), and may be 0.010 or more, 0.020 or more, or 0.030 or more. In addition, the molar ratio ([NCO] / [OH]) can be, for example, 1.0 or less, and may be 0.10 or less. By limiting the molar ratio to a predetermined value or less, a crosslinked structure suitable for greatly increasing the adhesive strength after heating relative to the adhesive strength at the initial stage of application can be preferably formed. In some preferred embodiments, the molar ratio ([NCO] / [OH]) is 0.030 or less, more preferably 0.015 or less, even more preferably 0.012 or less (e.g., 0.009 or less), and may be 0.005 or less. In the adhesive layer, the isocyanate group and the hydroxyl group may exist in a state in which at least a part of them are chemically bonded (crosslinked). More specifically, the isocyanate group may exist in a state in which they are chemically bonded (crosslinked) with the hydroxyl group. On the other hand, the hydroxyl group may exist in a state in which a part of them is chemically bonded with the isocyanate group, and another part is not chemically bonded (crosslinked) with the isocyanate group.

[0119] In some preferred embodiments, the adhesive layer contains a catalyst. The catalyst can be added for the purpose of promoting the curing of the adhesive layer during the formation of the adhesive layer, typically for the purpose of more effectively proceeding with any of the crosslinking reactions described above. Therefore, the catalyst is also called a curing catalyst or a crosslinking catalyst. By adding a catalyst, the initial curing is promoted, and side reactions that cause the generation of bubbles on the surface of the adhesive layer can be suppressed. Examples of catalysts include organometallic compounds such as iron-based catalysts, tin-based catalysts, titanium-based catalysts, zirconium-based catalysts, lead-based catalysts, cobalt-based catalysts, and zinc-based catalysts, and tertiary amine compounds. These can be used alone or in combination of two or more. Among them, iron-based catalysts and tin-based catalysts are preferred from the perspective of the balance between reaction rate and pot life, and iron-based catalysts are particularly preferred.

[0120] Examples of the iron-based catalyst include iron acetylacetonate, iron 2-ethylhexanoate, etc. The iron-based catalysts may be used alone or in combination of two or more.

[0121] Examples of tin catalysts include dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin maleate, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin sulfide, tributyltin methoxide, tributyltin acetate, triethyltin ethoxide, tributyltin ethoxide, dioctyltin oxide, dioctyltin dilaurate, tributyltin chloride, tributyltin trichloroacetate, tin 2-ethylhexanoate, etc. The tin catalysts can be used alone or in combination of two or more.

[0122] The amount of catalyst used is not particularly limited, and can be, for example, 0.0001 parts by weight or more, preferably 0.001 parts by weight or more, more preferably 0.003 parts by weight or more, even more preferably 0.006 parts by weight or more, and particularly preferably 0.008 parts by weight or more, relative to 100 parts by weight of polymer (A). By using an appropriate amount of catalyst, the generation of bubbles from the adhesive layer is suppressed, and a smooth adhesive surface is easily obtained. In addition, the amount of catalyst used relative to 100 parts by weight of polymer (A) can be, for example, 1 part by weight or less, and may be 0.1 parts by weight or less. In some preferred embodiments, the amount of catalyst used relative to 100 parts by weight of polymer (A) is 0.03 parts by weight or less, more preferably 0.02 parts by weight or less, even more preferably 0.01 parts by weight or less, and may be 0.005 parts by weight or less. By appropriately limiting the content of catalyst relative to 100 parts by weight of polymer (A), it is easy to realize a suitable increase in adhesive strength.

[0123] Although not particularly limited, when a catalyst is used in a configuration in which the pressure-sensitive adhesive layer contains a hydroxyl group-containing monomer as a monomer unit, the amount of catalyst used is, for example, such that the molar ratio of the catalyst to the hydroxyl group ([catalyst] / [OH]) contained in the pressure-sensitive adhesive layer is 1.0×10 -6 The amount can be set to 1.0×10 or more, preferably 1.0×10 -5 More preferably, 1.0×10 -4 More preferably, 2.0×10 -4 More preferably, 3.0×10 -4 By using an appropriate amount of catalyst, the generation of bubbles from the adhesive layer is suppressed, and a smooth adhesive surface is easily obtained. In addition, the molar ratio ([catalyst] / [OH]) is, for example, 5.0×10 -2 It can be 5.0 x 10 -3 In some preferred embodiments, the molar ratio ([catalyst] / [OH]) is 3.0×10 -3 More preferably, it is 1.0×10 -3 Less than 5.0×10, more preferably -4 is less than or equal to 3.0 x 10 -4 By appropriately limiting the catalyst content, it is easy to realize a suitable increase in adhesive strength.

[0124] (tackifier resin) The adhesive layer may contain a tackifier resin as necessary. The tackifier resin is not particularly limited, but may be, for example, a rosin-based tackifier resin, a terpene-based tackifier resin, a phenol-based tackifier resin, a hydrocarbon-based tackifier resin, a ketone-based tackifier resin, a polyamide-based tackifier resin, an epoxy-based tackifier resin, or an elastomer-based tackifier resin. The tackifier resin may be used alone or in combination of two or more.

[0125] The content of the tackifier resin is not particularly limited, and can be set so as to exhibit appropriate adhesive performance depending on the purpose and application. The content of the tackifier resin (when two or more tackifier resins are included, the total amount thereof) relative to 100 parts by weight of the polymer (A) can be, for example, about 5 to 500 parts by weight. In addition, the technology disclosed herein can be preferably implemented in an embodiment in which the amount of the tackifier resin used is limited. For example, the content of the tackifier resin relative to 100 parts by weight of the polymer (A) can be less than 20 parts by weight, may be less than 10 parts by weight, may be less than 3 parts by weight, or may be less than 1 part by weight (0 parts by weight to less than 1 part by weight), and in some embodiments, the adhesive layer does not substantially contain a tackifier resin.

[0126] In addition, the adhesive layer in the technology disclosed herein may contain, as necessary, known additives that can be used in adhesives, such as leveling agents, plasticizers, softeners, colorants (dyes, pigments, etc.), fillers, antistatic agents, antioxidants, UV absorbers, antioxidants, light stabilizers, and preservatives, provided that the effects of the present invention are not significantly impeded.

[0127] The adhesive layer constituting the reinforcing film disclosed herein may be a cured layer of an adhesive composition. That is, the adhesive layer may be formed by applying (for example, coating) an aqueous dispersion type, solvent type, photocurable type, hot melt type, or other adhesive composition to a suitable surface, and then appropriately carrying out a curing treatment. When two or more types of curing treatments (drying, crosslinking, polymerization, cooling, etc.) are performed, these can be performed simultaneously or in multiple stages. In an adhesive composition using a partial polymer (polymer syrup) of a monomer raw material, typically, a final copolymerization reaction is performed as the curing treatment. That is, the partial polymer is subjected to a further copolymerization reaction to form a complete polymer. For example, in the case of a photocurable adhesive composition, light irradiation is performed. If necessary, a curing treatment such as crosslinking or drying may be performed. For example, if a photocurable adhesive composition needs to be dried, it is recommended to perform photocuring after drying. In an adhesive composition using a complete polymer, typically, a treatment such as drying (heat drying) or crosslinking is performed as the curing treatment if necessary.

[0128] The pressure-sensitive adhesive composition can be applied using a conventional coater such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater or a spray coater.

[0129] The thickness of the adhesive layer is not particularly limited, and can be, for example, 6 μm or more. In some embodiments, the thickness of the adhesive layer may be 8 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more or more than 20 μm. The adhesive strength after heating tends to increase due to the increase in the thickness of the adhesive layer. In some embodiments, the thickness of the adhesive layer may be, for example, 300 μm or less, 200 μm or less, 150 μm or less, 100 μm or less, 70 μm or less, 50 μm or less, or 40 μm or less. It may be advantageous from the viewpoint of thinning the reinforcing film and preventing cohesive failure of the adhesive layer, etc., if the thickness of the adhesive layer is not too large. A reinforcing film having an adhesive layer having a thickness within the above-mentioned range may have a well-balanced adhesive property such as adhesive strength, bending recovery, and bending retention. In addition, in the case of a reinforcing film having a first pressure-sensitive adhesive layer and a second pressure-sensitive adhesive layer on the first and second surfaces of a substrate, the thickness of the above-mentioned pressure-sensitive adhesive layer can be applied to at least the thickness of the first pressure-sensitive adhesive layer. The thickness of the second pressure-sensitive adhesive layer can also be selected from the same range. In addition, in the case of a reinforcing film without a substrate, the thickness of the reinforcing film is the same as the thickness of the pressure-sensitive adhesive layer.

[0130] <Supporting base material> The reinforcing film according to some embodiments may be in the form of a substrate-attached adhesive sheet having an adhesive layer on one or both sides of the substrate. The material of the substrate is not particularly limited and can be appropriately selected according to the purpose and mode of use of the reinforcing film. Non-limiting examples of substrates that can be used include resin films such as plastic films; foam sheets made of foams such as polyurethane foam, polyethylene foam, and polychloroprene foam; woven and nonwoven fabrics made by single or mixed spinning of various fibrous materials (natural fibers such as hemp and cotton, synthetic fibers such as polyester and vinylon, semi-synthetic fibers such as acetate, etc.); papers such as Japanese paper, fine paper, craft paper, and crepe paper; metal foils such as aluminum foil and copper foil; and the like. The substrate may be a composite of these. Examples of such composite substrates include substrates having a structure in which metal foil and the above-mentioned plastic film are laminated, plastic substrates reinforced with inorganic fibers such as glass cloth, and the like.

[0131] As the substrate of the reinforcing film disclosed herein, various film substrates can be preferably used. The film substrate may be a porous substrate such as a foam film or a nonwoven sheet, or may be a nonporous substrate, or may be a substrate having a structure in which a porous layer and a nonporous layer are laminated. In some embodiments, the film substrate may preferably be one that includes a resin film that can independently maintain its shape (self-supporting or independent) as a base film. Here, the term "resin film" refers to a resin film that has a nonporous structure and typically does not substantially contain air bubbles (voidless). Therefore, the resin film is a concept that is distinguished from foam films and nonwoven fabrics. As the resin film, one that can independently maintain its shape (self-supporting or independent) can be preferably used. The resin film may be a single-layer structure, or may be a multi-layer structure of two or more layers (for example, a three-layer structure).

[0132] Examples of resin materials constituting the resin film include polyester, polyolefin, polyamide (PA) such as nylon 6, nylon 66, and partially aromatic polyamide, polyimide (PI), polyamideimide (PAI), polyetheretherketone (PEEK), polyethersulfone (PES), polyphenylene sulfide (PPS), polycarbonate (PC), polyurethane (PU), ethylene-vinyl acetate copolymer (EVA), fluororesin such as polytetrafluoroethylene (PTFE), acrylic resin, polyacrylate, polystyrene, polyvinyl chloride, and polyvinylidene chloride. The resin film may be formed using a resin material containing only one of these resins, or may be formed using a resin material containing two or more of them blended together. The resin film may be unstretched or stretched (for example, uniaxially or biaxially stretched).

[0133] Suitable examples of resin materials constituting the resin film include polyimide-based resins, polyester-based resins, PPS resins, and polyolefin-based resins. Here, polyimide-based resins refer to resins containing more than 50% by weight of polyimide. Similarly, polyester-based resins refer to resins containing more than 50% by weight of polyester, PPS resins refer to resins containing more than 50% by weight of PPS, and polyolefin-based resins refer to resins containing more than 50% by weight of polyolefin.

[0134] Specific examples of polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), and polybutylene naphthalate.

[0135] As the polyolefin resin, one type of polyolefin can be used alone, or two or more types of polyolefins can be used in combination. The polyolefin can be, for example, a homopolymer of an α-olefin, a copolymer of two or more types of α-olefins, or a copolymer of one or more types of α-olefins and other vinyl monomers. Specific examples include polyethylene (PE), polypropylene (PP), poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene copolymers such as ethylene-propylene rubber (EPR), ethylene-propylene-butene copolymers, ethylene-butene copolymers, ethylene-vinyl alcohol copolymers, and ethylene-ethyl acrylate copolymers. Both low density (LD) polyolefins and high density (HD) polyolefins can be used. Examples of polyolefin resin films include non-oriented polypropylene (CPP) film, biaxially oriented polypropylene (OPP) film, low-density polyethylene (LDPE) film, linear low-density polyethylene (LLDPE) film, medium-density polyethylene (MDPE) film, high-density polyethylene (HDPE) film, polyethylene (PE) film made by blending two or more types of polyethylene (PE), and PP / PE blend film made by blending polypropylene (PP) and polyethylene (PE).

[0136] Specific examples of resin films that can be preferably used as the base film of the reinforcing film disclosed herein include a PI film, a PET film, a PEN film, a PPS film, a PEEK film, a CPP film, and an OPP film.

[0137] The resin film may contain known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, slip agents, antiblocking agents, etc., as necessary, within the range that does not significantly impair the effects of the present invention. The amount of the additives to be added is not particularly limited, and can be appropriately set depending on the purpose, etc.

[0138] The method for producing the resin film is not particularly limited, and may be any of the conventionally known general resin film forming methods, such as extrusion molding, inflation molding, T-die casting, and calendar roll molding.

[0139] The substrate may be substantially composed of such a base film. Alternatively, the substrate may include an auxiliary layer in addition to the base film. Examples of the auxiliary layer include an optical property adjusting layer (e.g., a coloring layer, an anti-reflection layer), a printing layer or a lamination layer for imparting a desired appearance to the substrate, an antistatic layer, an undercoat layer, a peeling layer, and other surface treatment layers.

[0140] The thickness of the substrate is not particularly limited and may be selected according to the purpose and mode of use of the reinforcing film. The thickness of the substrate may be, for example, 1000 μm or less. In some embodiments, from the viewpoint of the handling and processability of the reinforcing film, the thickness of the substrate may be, for example, 500 μm or less, 300 μm or less, 250 μm or less, or 200 μm or less. In some embodiments, from the viewpoint of miniaturization and weight reduction of the product to which the reinforcing film is applied, the thickness of the substrate may be, for example, 160 μm or less, 130 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, 60 μm or less, 50 μm or less, 25 μm or less, 10 μm or less, or 5 μm or less. When the thickness of the substrate is reduced, the flexibility of the reinforcing film and its ability to follow the surface shape of the adherend tend to be improved. In addition, from the viewpoint of handling and processability, the thickness of the substrate may be, for example, 2 μm or more, 5 μm or more, 10 μm or more, 20 μm or more, 25 μm or more, or more than 25 μm. In some embodiments, the thickness of the substrate may be, for example, 30 μm or more, 35 μm or more, 55 μm or more, 70 μm or more, 75 μm or more, 90 μm or more, or 120 μm or more. For example, in the reinforcing film, a substrate having a thickness of 30 μm or more may be preferably used.

[0141] The first surface of the substrate may be subjected to a conventionally known surface treatment, such as a corona discharge treatment, a plasma treatment, an ultraviolet irradiation treatment, an acid treatment, an alkali treatment, or the formation of an undercoat layer by applying an undercoat agent (primer), if necessary. Such a surface treatment may be a treatment for improving the anchoring property of the pressure-sensitive adhesive layer to the substrate. For example, in a reinforcing film having a substrate containing a resin film as a base film, a substrate subjected to such an anchoring property improvement treatment may be preferably used. The above surface treatments may be applied alone or in combination. The composition of the primer used to form the undercoat layer is not particularly limited, and may be appropriately selected from known ones. The thickness of the undercoat layer is not particularly limited, but is usually appropriate to be about 0.01 μm to 1 μm, and preferably about 0.1 μm to 1 μm. Other treatments that may be applied to the first surface of the substrate as necessary include an antistatic layer forming treatment, a colored layer forming treatment, a printing treatment, and the like.

[0142] When the reinforcing film disclosed herein is in the form of a single-sided pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer only on the first surface of the substrate, the second surface of the substrate may be subjected to a conventionally known surface treatment such as a release treatment or an antistatic treatment, if necessary. For example, by surface treating the back surface of the substrate with a release treatment agent (typically by providing a release layer made of a release treatment agent), the unwinding force of the reinforcing film wound in a roll shape can be reduced. As the release treatment agent, a silicone-based release treatment agent, a long-chain alkyl-based release treatment agent, an olefin-based release treatment agent, a fluorine-based release treatment agent, a fatty acid amide-based release treatment agent, molybdenum sulfide, silica powder, etc. can be used. In addition, for the purpose of improving printability, reducing light reflectivity, improving overlapping adhesion, etc., the second surface of the substrate may be subjected to a corona discharge treatment, a plasma treatment, an ultraviolet irradiation treatment, an acid treatment, an alkali treatment, etc. In addition, in the case of a double-sided pressure-sensitive adhesive sheet, the second surface of the substrate may be subjected to a surface treatment similar to those exemplified above as the surface treatment that can be applied to the first surface of the substrate, if necessary. The surface treatment applied to the first surface of the substrate and the surface treatment applied to the second surface may be the same or different.

[0143] <Characteristics of the reinforcing film> The reinforcing film disclosed herein has an initial adhesive strength (N) measured after being attached to a stainless steel plate and kept at 23° C. for 30 minutes. 23 It is preferable that the adhesive force N is limited to a predetermined value or less. 23 is, for example, preferably less than 500 gf / 25 mm, more preferably less than 400 gf / 25 mm, even more preferably less than 300 gf / 25 mm, particularly preferably 250 gf / 25 mm or less (for example, 200 gf / 25 mm or less), and may be 150 gf / 25 mm or less. 23 A low adhesive strength N is preferable from the viewpoint of reworkability. 23 The lower limit of the adhesive strength N is not particularly limited, and may be, for example, 0.1 gf / 25 mm or more. From the viewpoints of ease of application to the adherend and prevention of positional deviation before the adhesive strength increases, etc. 23 In order to improve the adhesive strength after heating, it is usually appropriate that the adhesive strength N is 10 gf / 25 mm or more. 23 may be, for example, 20 gf / 25 mm or more, 50 gf / 25 mm or more, 80 gf / 25 mm or more, or 100 gf / 25 mm or more (for example, 150 gf / 25 mm or more).

[0144] Adhesive force N 23 [gf / 25mm] is determined by pressing the film against a stainless steel (SUS) plate as an adherend, leaving it in an environment of 23°C and 50% RH for 30 minutes, and then measuring the 180° peel adhesive strength in the same environment (i.e., at 23°C) at a peel angle of 180° and a tensile speed of 300mm / min. SUS304BA plate is used as the adherend. When making the measurement, if necessary, the reinforcing film to be measured can be reinforced by attaching an appropriate backing material (e.g., a PET film with a thickness of about 25μm). Adhesive strength N 23 More specifically, the initial adhesive strength can be measured in accordance with the method for measuring the initial adhesive strength described in the Examples section below.

[0145] The reinforcing film disclosed herein has an adhesive strength that increases when heated, and has an adhesive strength of, for example, N60 That is, the adhesive strength measured at 23° C. after being attached to a stainless steel plate and kept at 60° C. for 60 minutes may be 300 gf / 25 mm or more. In some embodiments, the adhesive strength N 60 The adhesive strength of a reinforcing film satisfying this characteristic is increased to a predetermined value or more by heating after being attached to an adherend. According to the technology disclosed herein, it is possible to obtain a strong adhesive strength by heating. In some preferred embodiments, the adhesive strength N 60 is 600gf / 25mm or more, more preferably 700gf / 25mm or more, may be 800gf / 25mm or more, or may be 900gf / 25mm or more. 60 There is no particular upper limit to the adhesive strength N. In some embodiments, from the viewpoint of ease of production of the reinforcing film and economic efficiency, 60 may be, for example, 3000 gf / 25 mm or less, 1500 gf / 25 mm or less, or 1000 gf / 25 mm or less.

[0146] Adhesive force N 60 [gf / 25mm] is determined by pressing the adhesive to a SUS plate as an adherend, keeping it in an environment of 60°C for 60 minutes, then leaving it in an environment of 23°C and 50% RH for 30 minutes, and then measuring the 180° peel adhesive strength in the same environment at a peel angle of 180° and a pulling speed of 300mm / min. 23 As in the previous example, a SUS304BA plate is used. When making the measurement, if necessary, the reinforcing film to be measured can be reinforced by attaching an appropriate backing material (for example, a PET film with a thickness of about 25 μm). Adhesive strength N 60 More specifically, the adhesive strength after heating can be measured in accordance with the method for measuring the adhesive strength after heating described in the Examples below.

[0147] Adhesive force N 23 Adhesive strength N against [gf / 25mm] 60 [gf / 25mm] ratio, i.e., adhesive strength increase ratio N 60 / N 23is not particularly limited, and in some embodiments, N 60 / N 23 is suitably 1.5 or more, preferably 2.0 or more, more preferably 2.5 or more, and even more preferably 3.0 or more (e.g., 3.5 or more), and may be greater than 5.0 (e.g., greater than 7.0). 60 / N 23 A reinforcing film with a large N exhibits good reworkability at the initial stage of application, and the adhesive strength can be significantly increased by subsequent heating or other measures. 60 / N 23 The upper limit of is not particularly limited, and is usually 100 or less. From the viewpoint of ease of production of the reinforcing film and economic efficiency, it may be 30 or less, 15 or less, or 10 or less. In some embodiments, N 60 / N 23 may be, for example, 5 or less, 3 or less, or 2 or less.

[0148] The adhesive strength after heating of the reinforcing film disclosed herein represents one characteristic of the reinforcing film, and does not limit the use of the reinforcing film. In other words, the use of the reinforcing film disclosed herein is not limited to the use of the reinforcing film at 60°C for 60 minutes, and the reinforcing film can be used in a mode in which heating is not particularly performed to a temperature above room temperature (usually 20°C to 30°C, typically 23°C to 25°C). Even in such a use mode, the adhesive strength increases over the long term, and strong bonding can be achieved. In addition, the reinforcing film disclosed herein can be heated at a temperature above 30°C (for example, about 50 to 70°C) or higher than 60°C at any timing after attachment to promote an increase in adhesive strength. The heating temperature in such a heat treatment is not particularly limited, and can be set in consideration of workability, economy, heat resistance of the base material of the reinforcing film and the adherend, and the like. The heating temperature may be, for example, less than 150°C, 120°C or less, 100°C or less, 80°C or less, or 70°C or less. The heating temperature can be, for example, 40°C or higher, 45°C or higher, 50°C or higher, 55°C or higher, 60°C or higher, or 70°C or higher, and may be 80°C or higher, or 100°C or higher. The heating time is not particularly limited, and may be, for example, 3 hours or less, 1 hour or less, 30 minutes or less, or 10 minutes or less. The heating time may be, for example, 1 minute or more, 15 minutes or more, 30 minutes or more, or 1 hour or more. Alternatively, the heating treatment may be performed for a longer period of time as long as no significant thermal deterioration occurs in the reinforcing film or the adherend. The heating treatment may be performed all at once, or may be performed in multiple steps.

[0149] <Reinforcing film with substrate> When the reinforcing film disclosed herein is in the form of a pressure-sensitive adhesive sheet with a substrate, the thickness of the reinforcing film may be, for example, 1000 μm or less, 600 μm or less, 350 μm or less, or 250 μm or less. In view of the miniaturization, weight reduction, thinning, etc. of the product to which the reinforcing film is applied, in some embodiments, the thickness of the reinforcing film may be, for example, 200 μm or less, 175 μm or less, 140 μm or less, 120 μm or less, or 100 μm or less (for example, less than 100 μm). In addition, in view of the handleability, etc., the thickness of the reinforcing film may be, for example, 5 μm or more, 10 μm or more, 15 μm or more, 20 μm or more, 25 μm or more, or 30 μm or more. In some embodiments, the thickness of the reinforcing film may be, for example, 50 μm or more, 60 μm or more, 80 μm or more, 100 μm or more, or 120 μm or more. The upper limit of the thickness of the reinforcing film is not particularly limited. The thickness of the reinforcing film refers to the thickness of the portion attached to the adherend. For example, in the case of the reinforcing film 1 having the configuration shown in FIG. 1, the thickness refers to the thickness from the adhesive surface 21A of the reinforcing film 1 to the second surface 10B of the substrate 10, and does not include the thickness of the release liner 31.

[0150] The reinforcing film disclosed herein can be suitably implemented, for example, in an embodiment in which the thickness Ts of the support substrate is greater than the thickness Ta of the adhesive layer, that is, in an embodiment in which Ts / Ta is greater than 1. Although not particularly limited, Ts / Ta may be, for example, 1.1 or more, 1.2 or more, 1.5 or more, or 1.7 or more. For example, an increase in Ts / Ta tends to make it easier to exhibit good effects even when the reinforcing film is made thinner. In some embodiments, Ts / Ta may be 2 or more (e.g., greater than 2), 2.5 or more, or 2.8 or more. In addition, Ts / Ta may be, for example, 50 or less, or 20 or less. From the viewpoint of making it easier to exhibit high post-heat adhesive strength even when the reinforcing film is made thinner, Ts / Ta may be, for example, 10 or less, 8 or less, or 5 or less.

[0151] The pressure-sensitive adhesive layer is preferably fixed to the support substrate. Here, the term "fixed" refers to the fact that, in a reinforcing film whose adhesive strength has increased after being attached to an adherend, the pressure-sensitive adhesive layer exhibits sufficient anchoring properties to the support substrate to such an extent that peeling does not occur at the interface between the pressure-sensitive adhesive layer and the support substrate when the reinforcing film is peeled off from the adherend. A substrate-attached reinforcing film in which the pressure-sensitive adhesive layer is fixed to the support substrate can firmly integrate the adherend and the support substrate. A suitable example of a reinforcing film in which the pressure-sensitive adhesive layer is fixed to the substrate is a reinforcing film in which peeling (anchor failure) does not occur between the pressure-sensitive adhesive layer and the support substrate when the above-mentioned post-heating adhesive strength is measured. A reinforcing film in which anchor failure does not occur when the post-heating adhesive strength is measured is a suitable example of a reinforcing film in which the pressure-sensitive adhesive layer is fixed to the substrate.

[0152] The reinforcing film disclosed herein can be preferably produced by a method including, for example, contacting a liquid pressure-sensitive adhesive composition with a first surface of a substrate and curing the pressure-sensitive adhesive composition on the first surface to form a pressure-sensitive adhesive layer in this order. The curing of the pressure-sensitive adhesive composition may involve one or more of drying, crosslinking, polymerization, cooling, etc. of the pressure-sensitive adhesive composition. According to the method of curing a liquid pressure-sensitive adhesive composition on the first surface of a substrate to form a pressure-sensitive adhesive layer, the anchoring property of the pressure-sensitive adhesive layer to the substrate can be improved compared to the method of placing the pressure-sensitive adhesive layer on the first surface of the substrate by bonding the cured pressure-sensitive adhesive layer to the first surface of the substrate. By utilizing this, a reinforcing film in which the pressure-sensitive adhesive layer is fixed to the substrate can be preferably produced.

[0153] In some embodiments, the method of contacting the liquid pressure-sensitive adhesive composition with the first surface of the substrate can be a method of directly applying the pressure-sensitive adhesive composition to the first surface of the substrate. By contacting the first surface (adhesive surface) of the pressure-sensitive adhesive layer cured on the first surface of the substrate with the release surface, a reinforcing film can be obtained in which the second surface of the pressure-sensitive adhesive layer is fixed to the first surface of the substrate and the first surface of the pressure-sensitive adhesive layer is in contact with the release surface. The release surface can be the surface of a release liner, the back surface of a substrate that has been subjected to a release treatment, or the like.

[0154] In addition, for example, in the case of a photocurable pressure-sensitive adhesive composition using a partial polymer (polymer syrup) of a monomer raw material, the pressure-sensitive adhesive composition may be applied to a release surface, and then the applied pressure-sensitive adhesive composition may be covered with a first surface of a substrate to bring the uncured pressure-sensitive adhesive composition into contact with the first surface of the substrate, and in this state, the pressure-sensitive adhesive composition sandwiched between the first surface of the substrate and the release surface may be irradiated with light to cure it, thereby forming a pressure-sensitive adhesive layer.

[0155] The above-mentioned methods are not intended to limit the method for producing the reinforcing film disclosed herein. In producing the reinforcing film disclosed herein, any suitable method capable of adhering the adhesive layer to the first surface of the substrate can be used alone or in combination of two or more. Examples of such methods include the method of curing a liquid adhesive composition on the first surface of the substrate to form an adhesive layer, as described above, and the method of performing a surface treatment on the first surface of the substrate to enhance the anchoring property of the adhesive layer. For example, when the anchoring property of the adhesive layer to the substrate can be sufficiently improved by providing an undercoat layer on the first surface of the substrate, the reinforcing film may be produced by laminating the cured adhesive layer to the first surface of the substrate. The anchoring property of the adhesive layer to the substrate can also be improved by selecting the material of the substrate or the composition of the adhesive. The anchoring property of the adhesive layer to the substrate can also be improved by applying a temperature higher than room temperature to a reinforcing film having an adhesive layer on the first surface of the substrate. The temperature applied to enhance the anchoring property may be, for example, about 35°C to 80°C, about 40°C to 70°C or higher, or about 45°C to 60°C.

[0156] When the reinforcing film disclosed herein is in the form of a pressure-sensitive adhesive sheet having a first pressure-sensitive adhesive layer provided on a first surface of a substrate and a second pressure-sensitive adhesive layer provided on a second surface of the substrate (i.e., a double-sided pressure-sensitive adhesive sheet with a substrate), the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer may have the same configuration or different configurations. When the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer have different configurations, the difference may be, for example, a difference in composition or structure (thickness, surface roughness, formation area, formation pattern, etc.). For example, the second pressure-sensitive adhesive layer may be a pressure-sensitive adhesive layer that does not contain polymer (B). In addition, the surface of the second pressure-sensitive adhesive layer (second pressure-sensitive adhesive surface) may have a surface elasticity modulus at 23°C outside the range of 1 to 20 kPa (for example, more than 20 kPa), and may be 30 kPa or more.

[0157] <Reinforcing film with release liner> The reinforcing film disclosed herein may take the form of an adhesive product in which the surface (adhesive surface) of the adhesive layer is in contact with the release surface of a release liner. Thus, this specification can provide a reinforcing film with a release liner, which includes any of the reinforcing films disclosed herein and a release liner having a release surface in contact with the adhesive surface of the reinforcing film.

[0158] The thickness of the release liner is not particularly limited, but is usually about 5 μm to 200 μm. When the thickness of the release liner is within the above range, it is preferable because it is easy to attach to the adhesive layer and easy to peel from the adhesive layer. In some embodiments, the thickness of the release liner may be, for example, 10 μm or more, 20 μm or more, 30 μm or more, or 40 μm or more. In addition, from the viewpoint of facilitating peeling from the adhesive layer, the thickness of the release liner may be, for example, 100 μm or less, or 80 μm or less. The release liner may be subjected to a known antistatic treatment such as a coating type, a kneading type, or a deposition type, as necessary.

[0159] The release liner is not particularly limited, and for example, a release liner having a release layer on the surface of a liner substrate such as a resin film or paper (which may be paper laminated with a resin such as polyethylene), or a release liner made of a resin film formed from a low-adhesion material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin resin (polyethylene, polypropylene, etc.) can be used. Since the surface smoothness is excellent, a release liner having a release layer on the surface of a resin film as a liner substrate, or a release liner made of a resin film formed from a low-adhesion material can be preferably used. The resin film is not particularly limited as long as it is a film that can protect the adhesive layer, and examples thereof include a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a polymethylpentene film, a polyvinyl chloride film, a vinyl chloride copolymer film, a polyester film (PET film, PBT film, etc.), a polyurethane film, and an ethylene-vinyl acetate copolymer film. The release layer can be formed using known release agents such as silicone-based release agents, long-chain alkyl-based release agents, olefin-based release agents, fluorine-based release agents, fatty acid amide-based release agents, molybdenum sulfide, silica powder, etc. The use of silicone-based release agents is particularly preferred.

[0160] The thickness of the release layer is not particularly limited, but is usually about 0.01 μm to 1 μm, and preferably about 0.1 μm to 1 μm. The method for forming the release layer is not particularly limited, and a known method can be appropriately adopted depending on the type of release treatment agent used, etc.

[0161] <Application> The reinforcing film provided by this specification can exhibit good reworkability, for example, in the initial stage after being attached to the adherend, and can contribute to suppressing a decrease in yield and improving the quality of products containing the reinforcing film. The adhesive strength of the reinforcing film can be greatly increased by aging or heating after being attached to the adherend. For example, by heating at an appropriate timing after being attached to the adherend, the reinforcing film can be firmly attached to the adherend. Taking advantage of such characteristics, the reinforcing film disclosed herein can be preferably used in various fields for the purpose of reinforcing members contained in various products.

[0162] The reinforcing film disclosed herein can be preferably used as a reinforcing film that is attached to an adherend and reinforces the adherend, for example, in the form of a substrate-attached pressure-sensitive adhesive sheet in which a pressure-sensitive adhesive layer is provided on at least the first surface of a film-like substrate having a first surface and a second surface. In such a reinforcing film, a film substrate containing a resin film as a base film can be preferably used. In addition, from the viewpoint of enhancing reinforcing performance, it is preferable that the pressure-sensitive adhesive layer is fixed to the first surface of the film-like substrate. For example, optical components used in optical products and electronic components used in electronic products are becoming highly integrated, smaller, lighter, and thinner, and multiple thin optical / electronic components with different linear expansion coefficients and thicknesses may be stacked. By attaching the above-mentioned reinforcing film to such components, it is possible to impart appropriate rigidity to the optical / electronic components. This makes it possible to suppress curling and curvature caused by stress that may occur between multiple components with different linear expansion coefficients and thicknesses during the manufacturing process and / or in the manufactured product. Furthermore, in the manufacturing process of optical products / electronic products, in the situation where thin optical / electronic components are subjected to shaping processing such as cutting as described above, by attaching a reinforcing film to the components, local stress concentration on the optical / electronic components accompanying processing can be alleviated, and the risk of cracks, breakage, peeling of laminated components, etc. Attaching a reinforcing member to an optical / electronic component and handling it can also be useful for alleviating local stress concentration during transportation, stacking, rotation, etc. of the components, and for preventing bending or bending due to the weight of the components. Furthermore, in the case of devices such as optical products and electronic products including the above-mentioned reinforcement film, when the devices are used by consumers in the market, even if the devices are subjected to unintentional stress such as when the devices are dropped, placed under a heavy object, or hit by a flying object, the inclusion of the reinforcement film in the devices can reduce stress on the devices. Therefore, the inclusion of the reinforcement film in the devices can improve the durability of the devices.

[0163] The reinforcing film disclosed herein may be preferably used in an embodiment in which it is attached to a member constituting various portable devices (portable devices). Here, "portable" does not mean that it is merely portable, but that it has a level of portability that allows an individual (average adult) to carry it relatively easily. Examples of portable devices herein include mobile phones, smartphones, tablet computers, notebook computers, various wearable devices, digital cameras, digital video cameras, audio devices (portable music players, IC recorders, etc.), calculators (calculators, etc.), portable game devices, electronic dictionaries, electronic organizers, electronic books, in-vehicle information devices, portable radios, portable televisions, portable printers, portable scanners, portable modems, and other portable electronic devices, as well as mechanical wristwatches, pocket watches, flashlights, hand mirrors, and the like. Examples of members constituting the above portable electronic devices may include optical films and display panels used in image display devices such as thin-layer displays such as liquid crystal displays and film-type displays. The reinforcing film disclosed herein may be preferably used in an embodiment in which it is attached to various members in automobiles, home appliances, and the like.

[0164] In addition, since the reinforcing film disclosed herein has bending recovery and bending retention, it can be preferably used in an embodiment in which it is attached to a member constituting an apparatus having a bendable element (for example, a flexible device such as a flexible display. It may also be called a rollable device or a foldable device.) by taking advantage of its characteristics. Examples of such an apparatus include the above-mentioned various mobile devices (portable devices). Examples of the members constituting the above-mentioned mobile electronic devices may include optical films and display panels used in image display devices such as liquid crystal displays and organic EL (electroluminescence) displays. The reinforcing film disclosed herein can be preferably used in such mobile electronic devices for reinforcing the members constituting the apparatus (typically, image display devices called flexible devices or foldable devices, etc.).

[0165] The reinforcing film disclosed herein is suitable for use in reinforcing optical members during production, transportation, etc., of optical members used as components of liquid crystal display panels, plasma display panels (PDPs), organic EL displays, etc. It is useful as a reinforcing film applied to optical members such as polarizing plates (polarizing films), wave plates, retardation plates, optical compensation films, brightness enhancement films, light diffusion sheets, and reflective sheets for liquid crystal display panels.

[0166] The use of the reinforcing film disclosed herein is not particularly limited, and can be used for various purposes such as imparting rigidity and impact resistance. The reinforcing film disclosed herein can be used not only for flexible device applications as described above, but also for other applications not including flexible devices. The fact that the reinforcing film has flex recovery and flex retention means that there are few restrictions on the range of application of the reinforcing film, which has a great practical advantage. EXAMPLES

[0167] Some examples of the present invention will be described below, but it is not intended that the present invention be limited to those specific examples. In the following description, "parts" and "%" are by weight unless otherwise specified.

[0168] [Synthesis of polymer (A)] (Synthesis Example A1) In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube and a condenser, 90.2 parts of 2-ethylhexyl acrylate (2EHA), 8.6 parts of 4-hydroxybutyl acrylate (4HBA), 1.2 parts of N-acryloylmorpholine (ACMO), 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and ethyl acetate as a polymerization solvent were charged, and nitrogen gas was introduced while gently stirring. The liquid temperature in the flask was kept at around 65 ° C., and the polymerization reaction was carried out for 6 hours to prepare an acrylic polymer A1 solution with a polymer concentration of 35%. The weight average molecular weight (Mw) of the acrylic polymer A1 was 540,000.

[0169] (Synthesis example A2) A solution of acrylic polymer A2 was obtained by carrying out solution polymerization in the same manner as in Synthesis Example A1, except that the monomer composition was changed to 2EHA / 4HBA / ACMO / butyl acrylate (BA)=86.1 parts / 9.7 parts / 1.8 parts / 2.4 parts.

[0170] (Synthesis example A3) A solution of acrylic polymer A3 was obtained by carrying out solution polymerization in the same manner as in Synthesis Example A1, except that the monomer composition was changed to BA / 4HBA=96 parts / 4 parts.

[0171] (Synthesis example A4) A solution of acrylic polymer A4 was obtained by carrying out solution polymerization in the same manner as in Synthesis Example A1, except that the monomer composition was changed to 2EHA / HEA / methyl methacrylate (MMA) / N-vinyl-2-pyrrolidone (NVP) = 65 parts / 15 parts / 7 parts / 13 parts.

[0172] [Synthesis of polymer (B)] 101.15 parts of ethyl acetate, 40 parts of MMA, 20 parts of n-butyl methacrylate (BMA), 20 parts of 2-ethylhexyl methacrylate (2EHMA), 8.7 parts of a polyorganosiloxane skeleton-containing methacrylate monomer having a functional group equivalent of 900 g / mol (trade name: X-22-174ASX, manufactured by Shin-Etsu Chemical Co., Ltd.), 11.3 parts of a polyorganosiloxane skeleton-containing methacrylate monomer having a functional group equivalent of 4600 g / mol (trade name: KF-2012, manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.8 parts of thioglycerol as a chain transfer agent were charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas introduction tube, a cooler, and a dropping funnel. Then, after stirring for 30 minutes under a nitrogen atmosphere at 70 ° C, 0.2 parts of AIBN were charged as a thermal polymerization initiator and reacted at 70 ° C for 3 hours. After stirring at 80° C. for 30 minutes, 0.1 part of AIBN was further added and reacted at 80° C. for 2 hours. Then, 0.05 part of AIBN was further added and reacted at 80° C. for 2 hours to obtain polymer B. The Mw of the obtained polymer B was 20,000.

[0173] The Mw of each of the above-mentioned polymers was measured under the following conditions using a GPC device (HLC-8220GPC, manufactured by Tosoh Corporation) and calculated in terms of polystyrene. [GPC conditions] Sample concentration: 0.2 wt% (tetrahydrofuran (THF) solution) Sample injection volume: 10μL ·Eluent: THF ·Flow rate: 0.6mL / min ·Measurement temperature: 40℃ ·column: Sample column: TSKguardcolumn SuperHZ-H (1 column) + TSKgel SuperHZM-H (2 columns) Reference column: TSKgel SuperH-RC (1 column) Detector: Differential refractometer (RI)

[0174] [Preparation of reinforcing film] <Example 1> 100 parts of acrylic polymer A1, 2.0 parts of polymer B, and 0.015 parts of isocyanate compound C1 (product name "Coronate HX", manufactured by Tosoh Corporation) as a crosslinking agent in terms of solid content were added, and the mixture was diluted with ethyl acetate so that the total solid content became 30%, thereby obtaining an acrylic adhesive solution according to this example. A release liner made of polyester resin with a thickness of 75 μm and silicone-treated on one side (product name "Diafoil MRF75", manufactured by Mitsubishi Chemical Corporation) was prepared, and the acrylic adhesive solution obtained above was applied to the silicone-treated surface, followed by drying at 130°C for 1 minute to form an adhesive layer with a thickness of 25 μm. Next, a 50 μm-thick polyimide substrate (product name "Upilex 50S", manufactured by Ube Industries, Ltd.) was attached to the surface of the obtained adhesive layer to obtain a reinforcing film according to this example. This reinforcing film has an adhesive layer on one side of the substrate, and has the form of an adhesive sheet with a release liner in which the release surface of a release liner is in contact with the adhesive surface. In addition, for the reinforcing film of this example, the molar ratio ([NCO] / [OH]) was calculated to be 0.001 from the OH amount (the number of moles of hydroxyl groups in the acrylic polymer A1) and the NCO amount (the number of moles of isocyanate groups in the isocyanate compound) in the adhesive layer.

[0175] <Examples 2 to 5> The amount of isocyanate compound C1 used was changed to 0.05 parts (Example 2), 0.10 parts (Example 3), 0.20 parts (Example 4), or 0.60 parts (Example 5) in terms of solid content relative to 100 parts of acrylic polymer A1 as shown in Table 1. An acrylic pressure-sensitive adhesive solution according to each example was obtained in the same manner as in Example 1, except that these acrylic pressure-sensitive adhesive solutions were used. A reinforcing film according to each example was prepared in the same manner as in Example 1, except that these acrylic pressure-sensitive adhesive solutions were used.

[0176] <Examples 6 to 9> The amount of polymer B used was changed to 0.4 parts (Example 6), 1.0 parts (Example 7), 3.0 parts (Example 8), or 6.0 parts (Example 9) relative to 100 parts of acrylic polymer A1, as shown in Table 1. An acrylic pressure-sensitive adhesive solution according to each example was obtained in the same manner as in Example 3, except that these acrylic pressure-sensitive adhesive solutions were used. A reinforcing film according to each example was prepared in the same manner as in Example 1, except that these acrylic pressure-sensitive adhesive solutions were used.

[0177] <Example 10> Except for using acrylic polymer A2 instead of acrylic polymer A1, an acrylic pressure-sensitive adhesive solution according to this example was obtained in the same manner as in Example 3. Except for using the obtained acrylic pressure-sensitive adhesive solution, a reinforcing film according to this example was produced in the same manner as in the production of the reinforcing film according to Example 1.

[0178] <Example 11> An acrylic adhesive solution according to this example was obtained in the same manner as in Example 1, except that an acrylic polymer A3 was used instead of the acrylic polymer A1, and an isocyanate compound C2 (product name "Takenate D110N", manufactured by Mitsui Chemicals, Inc.) was used as a crosslinking agent in an amount of 0.07 parts in terms of solid content per 100 parts of the acrylic polymer A3. A reinforcing film according to this example was produced in the same manner as in Example 1, except that the obtained acrylic adhesive solution was used.

[0179] <Examples 12 to 13> The amount of isocyanate compound C2 used was changed to 0.09 parts (Example 12) and 0.395 parts (Example 13) in terms of solid content relative to 100 parts of acrylic polymer A3 as shown in Table 1, but the same procedure was followed to obtain an acrylic pressure-sensitive adhesive solution according to each example in the same manner as in Example 11, except that these acrylic pressure-sensitive adhesive solutions were used. The reinforcing films according to each example were produced in the same manner as in Example 1, except that these acrylic pressure-sensitive adhesive solutions were used.

[0180] <Examples 14 to 18> In the preparation of the acrylic adhesive solution according to Example 3, in addition to the acrylic polymer A1, the polymer B, and the isocyanate compound C1, as shown in Table 1, 0.001 parts (Example 14), 0.005 parts (Example 15), 0.010 parts (Example 16), 0.020 parts (Example 17), and 0.050 parts (Example 18) of an iron catalyst (Nacem ferric, manufactured by Nippon Kagaku Sangyo Co., Ltd.) were further added in terms of solid content to 100 parts of the acrylic polymer A1, and the solution was diluted with ethyl acetate (98% of the solvent component) and acetylacetone (2% of the solvent component) so that the total solid content was 30%, to obtain an acrylic adhesive solution according to each example. The reinforcing film according to each example was prepared in the same manner as in the preparation of the reinforcing film according to Example 1, except that these acrylic adhesive solutions were used. Table 1 also shows the molar ratio ([catalyst] / [OH]) of the catalyst and hydroxyl group contained in the adhesive layer. The molar ratio ([catalyst] / [OH]) is a value calculated from the amount of OH in the pressure-sensitive adhesive layer (the number of moles of hydroxyl groups in the acrylic polymer A1) and the amount of catalyst (the number of moles of catalyst).

[0181] <Examples 19 to 20> Acrylic pressure-sensitive adhesive solutions of each example were obtained in the same manner as in Example 14, except that the amount of polymer B used was changed to 1.0 part (Example 19) or 3.0 parts (Example 20) per 100 parts of acrylic polymer A1, as shown in Table 1. Reinforcing films of each example were prepared in the same manner as in Example 1, except that these acrylic pressure-sensitive adhesive solutions were used.

[0182] <Comparative Example 1> 100 parts of acrylic polymer A1 and 0.05 parts of isocyanate compound C1 (trade name "Coronate HX", manufactured by Tosoh Corporation) as a crosslinking agent in terms of solid content were added, and diluted with ethyl acetate so that the total solid content was 30%, to obtain an acrylic adhesive solution according to this example. A reinforcing film according to this example was produced in the same manner as in Example 1, except that the obtained acrylic adhesive solution was used.

[0183] <Comparative Examples 2 to 3> The amount of isocyanate compound C1 used was changed to 0.10 part (Comparative Example 2) or 0.20 part (Comparative Example 3) in terms of solid content relative to 100 parts of acrylic polymer A1 as shown in Table 1. An acrylic pressure-sensitive adhesive solution according to each example was obtained in the same manner as in Comparative Example 1, except that these acrylic pressure-sensitive adhesive solutions were used. A reinforcing film according to each example was produced in the same manner as in Example 1, except that these acrylic pressure-sensitive adhesive solutions were used.

[0184] <Comparative Example 4> An acrylic adhesive solution according to this example was obtained in the same manner as in Comparative Example 1, except that acrylic polymer A4 was used instead of acrylic polymer A1, and 0.50 parts of isocyanate compound C2 (product name "Takenate D110N", manufactured by Mitsui Chemicals, Inc.) was used as a crosslinking agent in terms of solid content per 100 parts of acrylic polymer A4. A reinforcing film according to this example was produced in the same manner as in Example 1, except that the obtained acrylic adhesive solution was used.

[0185] <Comparative Examples 5 to 6> Acrylic pressure-sensitive adhesive solutions of each example were obtained in the same manner as in Comparative Example 4, except that the amount of isocyanate compound C2 used was changed to 1.10 parts (Comparative Example 5) or 2.50 parts (Comparative Example 6) in terms of solid content per 100 parts of acrylic polymer A4, as shown in Table 1. Reinforcing films of each example were prepared in the same manner as in the preparation of the reinforcing film of Example 1, except that these acrylic pressure-sensitive adhesive solutions were used.

[0186] <Comparative Example 7> In preparing the acrylic adhesive solution, in addition to the acrylic polymer A4 and the isocyanate compound C2, 2.0 parts of polymer B was added per 100 parts of the acrylic polymer A4 as shown in Table 1, but the same procedure as in Comparative Example 4 was used to obtain the acrylic adhesive solution of this example. The reinforcing film of this example was produced in the same manner as in the production of the reinforcing film of Example 1, except that the obtained acrylic adhesive solution was used.

[0187] <Comparative Examples 8 to 9> Acrylic pressure-sensitive adhesive solutions of each example were obtained in the same manner as in Comparative Example 7, except that the amount of isocyanate compound C2 used was changed to 1.10 parts (Comparative Example 8) or 2.50 parts (Comparative Example 9) in terms of solid content relative to 100 parts of acrylic polymer A4, as shown in Table 1. Reinforcing films of each example were prepared in the same manner as in the preparation of the reinforcing film of Example 1, except that these acrylic pressure-sensitive adhesive solutions were used.

[0188] <Evaluation> [Surface elastic modulus] The reinforcing film according to each example was aged at 50° C. for one day, and the surface elastic modulus was measured. The release liner protecting the adhesive surface was peeled off, and a nanoindenter device (Triboindenter manufactured by Hysitron Inc.) was used to press an indenter into the surface of the adhesive layer to a depth of 6 μm, and the maximum load (Pmax) [GPa / mm 2 This was converted into the formula: Surface hardness [GPa]=Pmax / A The surface hardness was calculated by substituting the above formula into the above formula, and the surface hardness was converted into [kPa] units and recorded as the surface elastic modulus at 23°C (23°C surface elastic modulus). The measurement conditions are as follows. In the above formula, A is the contact projected area of ​​the indenter [mm 2 ]. (Measurement conditions) Indenter approach speed: 5 μm / s Maximum displacement: 6μm Pushing speed: 5μm / s Pulling speed: 5μm / s Indenter used: Conical (spherical indenter: radius of curvature 10μm) Measurement method: Single indentation measurement Measurement temperature: room temperature (23℃)

[0189] [Bulk elastic modulus G' and tan δ] A release liner R1 (trade name "Diafoil MRF75", manufactured by Mitsubishi Chemical Corporation) made of polyester resin with a thickness of 75 μm and silicone-treated on one side was prepared, and the acrylic adhesive solution according to each example was applied to the silicone-treated surface, and dried at 130° C. for 1 minute to form an adhesive layer with a thickness of 25 μm. Next, the surface of the obtained adhesive layer was covered with a release liner R2 (trade name "Diafoil MRE75", manufactured by Mitsubishi Chemical Corporation) made of polyester resin with a thickness of 75 μm and silicone-treated on one side, with the silicone-treated surface facing the adhesive layer, and aging was performed at 50° C. for 1 day. Only the resulting adhesive layer was taken out and laminated to a thickness of about 1 mm, which was then punched out to a diameter of 8 mm to prepare a cylindrical pellet, which was used as a measurement sample. The above measurement sample was fixed to a φ8 mm parallel plate fixture, and the storage modulus G', loss modulus G'' and loss tangent tanδ were measured under the following conditions using a dynamic viscoelasticity measuring device (TA Instruments, "ARES"), and the storage modulus G' at 23°C was 23 [kPa], storage modulus G' at 80°C 80 [kPa] and tan δ at 80°C (loss modulus G″ at 80°C 80 / Storage modulus G' at 80℃ 80 ) was sought. Measurement mode: Shear mode Temperature range: -70℃~200℃ Heating rate: 5℃ / min Frequency: 1Hz The storage modulus G' corresponds to the portion stored as elastic energy when the material is deformed, and is an index showing the degree of hardness. The loss modulus G'' corresponds to the portion of energy lost that is dissipated due to internal friction, etc. when the material is deformed, and indicates the degree of viscosity.

[0190] [Initial adhesive strength] The reinforcing film according to each example was aged at 50°C for one day, and cut together with the release liner to a width of 25 mm x length of 140 mm to be used as a measurement sample. The release liner was peeled off from the measurement sample to expose the adhesive surface, and a 2 kg hand roller was rolled back and forth once to press the sample against a stainless steel plate (SUS304BA plate) as an adherend. The measurement sample thus pressed against the adherend was left at an environmental temperature of 23°C for 30 minutes, and then a tensile tester (Shimadzu Corporation, product name "Autograph AG-Xplus HS 6000mm / min high-speed model (AG-50NX plus)") was used to measure the load when the reinforcing film was peeled off from the adherend under the conditions of a peel angle of 180 degrees and a peel speed (tensile speed) of 300 mm / min, and the average load during measurement was recorded as the initial adhesive strength [gf / 25mm].

[0191] [Adhesive strength after heating] For the reinforcing film according to each example, a measurement sample was prepared in the same manner as in the above initial adhesive strength measurement, and was pressed against the adherend. The measurement sample pressed against the adherend was heated for 60 minutes at an environmental temperature of 60°C. After that, it was left for 30 minutes at an environmental temperature of 23°C, and the load when the reinforcing film was peeled from the adherend was measured using a tensile tester (manufactured by Shimadzu Corporation, product name "Autograph AG-Xplus HS 6000mm / min high-speed model (AG-50NX plus)") under the conditions of a peel angle of 180 degrees and a peel speed (tensile speed) of 300mm / min, and the average load during measurement was recorded as the adhesive strength after heating [gf / 25mm].

[0192] [Flexion retention test] The reinforcing film according to each example was aged at 50°C for one day, and then the release liner was peeled off, and a 25μm thick polyimide substrate (trade name "Upilex 25S", manufactured by Ube Industries, Ltd.) was attached to the exposed adhesive surface, and heated at 60°C for 60 minutes to adhere. Next, the obtained measurement sample (laminate) was fixed in a folded state so that the 25μm substrate side was on the inside and had a diameter of 6mm, and heated at 80°C for 15 hours. Then, it was left at room temperature (23°C) and confirmed to have cooled sufficiently, and then the fixing of the folded state of the measurement sample was released, and within 10 minutes from the release of the fixing, the bending angle [°] of the folded measurement sample was measured using a protractor to evaluate the bending recovery. The bending angle is the opening angle of the measurement sample (the angle at which the measurement sample opens from the folded state), and the closer to 180° the better the bending recovery, and the closer to 0° the bending angle the worse the bending recovery. Next, to evaluate the bending retention, the presence or absence of "peeling" at the bent portion of the measurement sample was visually confirmed. When no "peeling" was observed, it was rated as "G (Good)", and when "peeling" was observed, it was rated as "P (Poor)".

[0193] [Check for air bubbles] The reinforcing film of each example was aged at 50°C for one day, then cut to a size of 10 cm x 10 cm. The release liner was peeled off, and the amount of air bubbles generated per 10 cm square was visually checked and evaluated according to the following criteria. E (Excellent): No air bubbles were observed. G (Good): Bubbles were observed, but the area of ​​the surface where bubbles were generated was 50% or less per 10 cm square. A (Acceptable): Bubbles were observed in 50% or more of a 10 cm square area. However, the level was not problematic for practical use.

[0194] The evaluation results for the reinforcing film of each example are shown in Table 1. Table 1 also shows an outline of the composition of the pressure-sensitive adhesive layer of each example.

[0195] [Table 1]

[0196] As shown in Table 1, the pressure-sensitive adhesives according to Examples 1 to 20 contained polymer (A) and polymer (B), and had a low initial adhesive strength compared to Comparative Examples 1 to 6, which did not contain the polymer (B). The pressure-sensitive adhesives according to Examples 1 to 20 also showed a large increase in adhesive strength after heating. Furthermore, the reinforcing films according to Examples 1 to 20 had pressure-sensitive adhesive layers with a surface elastic modulus at 23°C in the range of 1 to 20 kPa, and also showed good flex recovery and flex retention. On the other hand, in Comparative Examples 4 to 9, in which the surface elastic modulus at 23°C was outside the range of 1 to 20 kPa, peeling was observed in the flex retention test.

[0197] More specifically, a comparison of Examples 1 to 5 showed that the higher the 23°C surface elasticity of the adhesive layer was in the range of 1 to 20 kPa, the more the flex recovery tended to improve, and the initial adhesive strength and the adhesive strength after heating tended to decrease. Examples 2 to 5 were superior to Example 1 in flex recovery, had a 23°C surface elasticity of 2 kPa or more, and had a tan δ at 80°C of 80 In Example 5, both the surface elastic modulus and bulk elastic modulus were high, the increase in adhesive strength after heating was relatively low compared to Examples 1 to 4, and there was a tendency for the amount of bubbles generated on the surface of the adhesive layer to be greater compared to the other Examples. The molar ratio of isocyanate groups to hydroxyl groups ([NCO] / [OH]) in the adhesive layer of Examples 2 to 4, which showed a better balance of improved initial adhesive strength, post-heating adhesive strength, flex recovery, and flex retention, was within the range of 0.002 to 0.03. In Examples 1 to 4, the 23°C bulk elastic modulus G' of the adhesive layer 23 No difference was observed. In addition, for Examples 2 and 3, the 80°C bulk elastic modulus G' 80 Regarding Examples 1 to 5, the 23° C. surface elastic modulus had a higher correlation with the flex recovery than the bulk elastic modulus.

[0198] In addition, a comparison of Examples 6 to 9 confirmed that the adhesive strength tends to decrease as the amount of polymer (B) used increases. In Examples 7 to 8, in which the amount of polymer (B) used was within the range of 0.5 to 5 parts per 100 parts of polymer (A), the initial adhesive strength was less than 500 gf / 25 mm, and the adhesive strength after heating was 500 gf / 25 mm or more, and the initial easy peelability at the time of application and the increase in adhesive strength after heating were better balanced. In addition, as the amount of polymer (B) used increased, the surface elastic modulus at 23°C tended to increase and the flex recovery property decreased. In addition, the results of Examples 10 to 13 confirmed that the desired effect could be achieved even if the type of polymer (A) of the adhesive or the type of crosslinking agent was changed. In Examples 10 to 11, the increase in adhesive strength after heating was greater than in Examples 12 to 13.

[0199] Furthermore, in Examples 14 to 20, the generation of air bubbles could be prevented by using a catalyst. Among them, the amount of the iron-based catalyst used was such that the molar ratio of the catalyst to the hydroxyl group ([catalyst] / [OH]) contained in the pressure-sensitive adhesive layer was 4.6E-5 (4.6×10 -5 )~9.2E-4(9.2×10 -4 In Examples 14 to 17 and 19 to 20, in which the amount of the adhesive was 0.01 to 0.05, the adhesive strength after heating increased significantly compared to the initial low adhesive strength. In particular, Example 19 showed the most balanced improvements in the initial adhesive strength, adhesive strength after heating, bending recovery, bending retention, and bubble generation prevention.

[0200] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]

[0201] 1,2,3 Reinforcement film 10 Supporting base material 10A front page 10B Second side 21 Adhesive layer (first adhesive layer) 21A Adhesive surface (first adhesive surface) 21B Adhesive surface (second adhesive surface) 22 Adhesive layer (second adhesive layer) 22A Adhesive surface (second adhesive surface) 31,32 Release liner 100,200,300 Reinforcement film with release liner

Claims

1. A reinforcing film having a pressure-sensitive adhesive layer, The pressure-sensitive adhesive layer contains a polymer (A) and a polymer (B), The polymer (A) is an acrylic polymer, The acrylic polymer contains 1% by weight or more and 20% by weight or less of monomer units derived from a hydroxyl group-containing monomer, The glass transition temperature T A of the polymer (A) is −80° C. or higher and lower than −35° C., The polymer (B) contains a monomer unit having a polyorganosiloxane skeleton and a (meth)acrylic monomer unit, the content of the polymer (B) in the pressure-sensitive adhesive layer is 0.1 to 30 parts by weight based on 100 parts by weight of the polymer (A); The pressure-sensitive adhesive layer contains an isocyanate-based crosslinking agent in an amount of 0.015 parts by weight or more and less than 1.0 part by weight based on 100 parts by weight of the polymer (A), The pressure-sensitive adhesive layer is a reinforcing film having a surface elastic modulus at 23° C. of 1 to 20 kPa.

2. The pressure-sensitive adhesive layer has a bulk modulus G' at 23°C. 23 is 10 to 200 kPa, and the bulk elastic modulus G' at 80°C 80 is 5 to 100 kPa, and tan δ at 80° C. 80 The reinforcing film according to claim 1, wherein the reinforcing film is 0.10 to 0.

60.

3. The reinforcing film according to claim 1 or 2, wherein the content of the polymer (B) in the pressure-sensitive adhesive layer is 0.5 to 5 parts by weight per 100 parts by weight of the polymer (A).

4. The reinforcing film according to any one of claims 1 to 3, wherein the molar ratio ([NCO] / [OH]) of isocyanate groups to hydroxyl groups contained in the pressure-sensitive adhesive layer is 0.002 to 0.

03.

5. The pressure-sensitive adhesive layer contains a catalyst, The molar ratio of the catalyst to the hydroxyl group ([catalyst] / [OH]) contained in the pressure-sensitive adhesive layer is 1.0×10 -6 ~5.0 x 10 -2 The reinforcing film according to any one of claims 1 to 4.

6. the catalyst is an iron-based catalyst; The molar ratio of the catalyst to the hydroxyl group ([catalyst] / [OH]) contained in the pressure-sensitive adhesive layer is 1.0×10 -4 ~1.0 x 10 -3 The reinforcing film according to claim 5 .

7. An optical member having the reinforcing film according to any one of claims 1 to 6 attached thereto.

8. An electronic component having the reinforcing film according to any one of claims 1 to 6 attached thereto.

Citation Information

Patent Citations

  • JP1988066199A

  • Simple herpesvirus glycoprotein and production thereof

    JP1988066200A

  • Shared memory access device

    JP1988073458A

  • Alkailine zinc storage battery

    JP1988076271A

  • Adhesive for optical film, adhesive layer for optical film, optical member and image display device

    JP2016108555A